Understanding the heat stress mitigation mechanisms during pollen development in Gossypium hirsutum L. - Rabia Habib; Zulqurnain Khan; Abdel-Halim Ghazy; Shoaib ur Rehman; Kotb A. Attia; Maria Siddique; Sajid Fiaz; Abdullah A. Al-Doss; Muhammad Abu Bakar Saddique; Ummara Waheed (Molecular Biology Reports, 2026)

Molecular characterization and vaccine matching of foot-and-mouth disease virus in Khyber Pakhtunkhwa, Pakistan - Muhammad Sajid; Muhammad Ali Syed; Abdul Kabir; Asghar Ali Kamboh; Muhammad Mumtaz Khan (Molecular Biology Reports, 2026)

Exogenous dopamine alleviates chilling injury of sapodilla (Manilkara zapota) fruit by modulating reactive oxygen species and ascorbate-glutathione cycle activities - Sajid Ali; Syed Muhammad Kashan Haider; Safina Naz; Hafiz Umer Javed; Aamir Nawaz; Shaghef Ejaz; Muhammad Shahzad Saleem (Postharvest Biology and Technology, 2026)

Facile synthesis of cobalt-iron layered double hydroxide and its derived mixed metal oxide for Congo red and Pb(II) remediation - Ramzan Akhtar; Adil Khan; Maria Gul; Mohsin Ali Raza Anjum; Iqra Rafique; Muhammad Rehan; Rashid Nazir Qureshi; Sajid Iqbal; Muhammad Saifullah (Colloids and Surfaces C: Environmental Aspects, 2026)

Nanoencapsulated chrysin protects against cadmium-induced renal tissue injury through modulation of oxidative stress, inflammatory responses, mitochondrial dysfunction, and apoptotic pathways - Ekramy M. Elmorsy; Ayat B. Al-Ghafari; Huda A. Al Doghaither; Muhammad Jan; Syed Sajid Hussain Shah; Asmara Syed; Eman M. Fawzy; Gehad E. Elshopakey (Tissue and Cell, 2026)

Nanoliposomal myricetin attenuates diabetic testicular tissue injury and cellular dysfunction via coordinated modulation of PI3K/AKT/mTOR/SREBP-1c, Nrf2/HO-1, NF-κB, and caspase signaling pathways - Ekramy M. Elmorsy; Ayat B. Al-Ghafari; Huda A. Al Doghaither; Muhammad Jan; Syed Sajid Hussain Shah; Asmara Syed; Basma H. Marghani; Gehad E. Elshopakey (Tissue and Cell, 2026)

Hydrodynamic response and tendon mechanics of tension-leg platform floating offshore wind turbines: A critical review and future perspectives - Haozhe Bai; Sami Ur Rehman; Abid Ali; Muhammad Irslan Khalid; Wei Shi; Fengmei Jing; Sajid Ali; Muhammad Asghar; Sheraz Hussain; Chunlei He (Ocean Engineering, 2026)

Scuffled bacterial cellulose with electron-rich sites: A robust adsorbent for simultaneous adsorption and reductive immobilization of toxic vanadium from aqueous solutions - Muhammad Younas; Jawad Ali; Yanan Chen; Yongjin Xiang; Ajmal Shahzad; Sajid Ullah; Jingtao Hou (Journal of Water Process Engineering, 2026)

Microbe-mediated drought stress alleviation: Fusarium verticillioides enhances maize growth by upregulation of physiological, biochemical, and molecular responses - Raid Ali; Humaira Gul; Mamoona Rauf; Sajid Ali; Muhammad Arif; Sumera Afzal Khan; Anwar Hussain; Bokyung Lee; Muhammad Hamayun (South African Journal of Botany, 2026)

Systems-level approaches to decoding chemical communication between crop plants and rhizosphere microbes in health and disease - Sajid Ali; Muhammad Siraj (Rhizosphere, 2026)

Structural and physiological adaptations conferring herbivory resistance in wild olive (Olea europaea L. subsp. cuspidata) - Faakeha Islam; Syed Mohsan Raza Shah; Farooq Ahmad; Mansoor Hameed; Sana Basharat; Sana Fatima; Ansar Mehmood; Zahida Parveen; Ansa Asghar; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Khawaja Shafique Ahmad (Physiology and Molecular Biology of Plants, 2026)

Reliability and sustainability of offshore wind turbine support structures in marine environments: a comprehensive review of failures, monitoring technologies, robotics, and predictive O&M - Sajid Ali; Muhammad Waleed; Daeyong Lee (Frontiers in Marine Science, 2026)
Offshore wind turbine support structures are increasingly required to operate in deeper and more demanding marine environments, where cyclic loading, hydrodynamic forcing, corrosion, scour, soil-structure interaction, and limited long-term monitoring continue to challenge structural reliability and lifecycle performance. This review synthesizes current knowledge on the reliability, degradation mechanisms, and maintenance needs of major offshore wind support-structure concepts, including monopiles, jackets, gravity-based foundations, tripods, hybrid fixed-bottom systems, spars, semi-submersibles, and tension-leg platforms. The study integrates findings from global field observations, reported failure cases, industrial practice, and recent advances in structural health monitoring, digital twins, robotics-assisted inspection, and AI-supported predictive operation and maintenance. Particular emphasis is placed on how marine environmental conditions and offshore loading processes influence structural response, fatigue behavior, corrosion-scour progression, and maintenance demand across fixed and floating systems. The review also identifies key gaps in long-term field validation, unified reliability assessment, and integrated monitoring-to-maintenance frameworks. By combining structural, operational, and marine-environment perspectives, this paper provides a consolidated reference for improving the durability, safety, and sustainability of offshore wind support structures within the broader context of marine renewable energy development.

Artificial intelligence, environmental innovation, and climate-related sustainable development: evidence from BRICS economies - Muhammad Sajid Mehmood; Lu Di; Qian Hongsheng; Ali Sohail; Gang Li; Qin Yaochen (Environment, Development and Sustainability, 2026)

Foliar Application of Boric Acid Modulates the Morpho-Physiological Attributes and Health Risk Factors of Turnip (Brassica rapa L.) Under Nickel Accumulation Stress - Fizza Sajid; Tahrim Ramzan; Muhammad Shahbaz; Arslan Haider; Ejaz Ahmad Waraich; Sundas Qadeer (Journal of Soil Science and Plant Nutrition, 2026)

Design and optimization of an autothermal solid oxide electrolysis cell reactor for efficient and economical solar-driven carbon dioxide reduction - Zihan Lin; Junjie Hou; Haoran Li; Qi Xia; Jiale Long; Zhouxin Pan; Muhammad Sajid Khan; Chen Chen (Journal of Cleaner Production, 2026)

Diesel engine performance enhancement using MXene nano-additives: An experimental study on efficiency and Pollutant Suppression - Mohd Danish; Sajid Ali; Syed Mohd Yahya; Rashid Ali; Suhaib Umer Ilyas; Sami Mansour Ghazali; Muhammad Faisal Rathore; Saeed Rubaiee (Fuel, 2026)

Innovations in functional layers of flexible perovskite solar cells: Progress toward efficient and commercially viable photovoltaics - Muhammad Sajid; Muhammad Abdel-Shakour; Prabakaran Selvaraj; Haibing Xie; Shern-Long Lee (Chemical Engineering Journal, 2026)

Assessment of functional trait variation in arid-zone plant families to evaluate indicator species for rehabilitation of degraded landscapes - Eisha Kanwal; Farooq Ahmad; Ansa Asghar; Ummar Iqbal; Anum Javaid; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Saba Gul; Muhammad Irshad; Khawaja Shafique Ahmad (The Science of Nature, 2026)

Plant-derived serine protease inhibitor peptides: in vitro antimicrobial and antiviral activities combined with in silico mechanistic insights - Shagufta Kamal; Asif Shahzad; Amna Kamal; Kanwal Rehman; Ismat Bibi; Muhammad Sajid Hamid Akash (Archives of Microbiology, 2026)

Multi-trait plant growth-promoting endophytic fusarium proliferatum from phoenix dactylifera enhanced wheat growth under drought stress condition - Salman Khan; Khalil Ur Rahman; Nida Karishma; Mamoona Rauf; Humaira Gul; Muhammad Hamayun; Abdulwahed Fahad Alrefaei; Faheem Anwar; Sajid Ali; Muhammad Arif (Acta Physiologiae Plantarum, 2026)

Species composition, relative abundance and seasonal variation of medically important mosquitoes in district Bajaur, Khyber Pakhtunkhwa, Pakistan - Halimullah; Waleeja Tur Rabbia; Naveeda Akhtar Qureshi; Waheed Ali Panhwar; Sajid Malik; Muhammad Ilyas (Acta Parasitologica, 2026)

From reagents to feedstocks: reprogramming heteroatom-containing molecules in modern organic synthesis - Jixiang Ni; Mohd. Aamir Bin Riyaz; Zhenyu An; Yang Lu; Sajid Muhammad; Yanguo Li; Ning Xi; Yufen Zhao (Molecular Diversity, 2026)

Nitrogen atom insertion and related skeletal editing strategies in aromatic heterocycles for drug discovery (2015–2025) - Jixiang Ni; Mohd. Aamir Bin Riyaz; Zhenyu An; Yang Lu; Sajid Muhammad; Chao Zhang; Ning Xi; Yufen zhao (Molecular Diversity, 2026)

Antimicrobial Plant Protein Patatin: Identification and In-Silico Analysis Through Phylogenetics and Molecular Docking - Sarah Tariq; Binish Khaliq; Hina Shaheen; Ahmad Riaz; Sumaira Rubbani; Muhammad Sajid Hamid Akash; Amjad Hussain; Muhammad Imran; Muhammad Arslan Javed; Ahmed Akrem; Sohaib Mehmood; Sajjad Azam (Agricultural Research, 2026)

Measurement-driven ULS redesign of a 15 MW semi-submersible floater under persistent wind-wave misalignment - Sajid Ali; Muhammad Waleed; Daeyong Lee (Ocean Engineering, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes” [Fuel 412 (2025) 138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Tailoring SrFeO3-δ cathodes via Nd and Cu doping for boosting ORR activity for high-performance LT-PCFCs below 600 °C - Naveed Mushtaq; Wu Ping; Badriah S. Almutairi; Sajid Rauf; M.A.K Yousaf Shah; Muhammad Sultan Irshad (Fuel, 2026)

Integrative screening of cotton genotypes against salt stress using pre-breeding and machine learning methods - Zunaira Anwar; Sajid Shokat; Allah Ditta; Muhammad Kashif Riaz Khan (Biocatalysis and Agricultural Biotechnology, 2026)

Lithology-driven machine and deep learning modelling for porosity prediction in shale reservoir systems using well logging data - Shaukat Khan; Zhishui Liu; Zhiqiang Lu; Wakeel Hussain; Muhammad Sajid; Manaf Muhammad; Abdul Wahid; Muhammad Ubaid Umar (Earth Science Informatics, 2026)

Synergistic Effects of Crop Residue Incorporation and Sesbania Green Manuring on Nitrogen Release, Ammonia Emission and Wheat Productivity in Rice-Wheat Cropping System - Hafiza Hafsa Iqbal; Sajid Mahmood; Abdul Rasul Awan; Muhammad Akhtar (Journal of Soil Science and Plant Nutrition, 2026)

Key determinants of volatile profile and bioactive potential in durian ( Durio zibethinus ) - Ziqi Lou; Alwateen Almarshad; Muhammad Sajid Arshad; Farhad Ahmadi; Hafiz A.R. Suleria (Critical Reviews in Food Science and Nutrition, 2026)

Corrigendum to “Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes”. [Fuel 412 (2025) 138022. doi: 10.1016/j.fuel.2025.138022] - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Desert treasures: a comprehensive review of the diversity, phytochemistry, ethnobotany, and conservation of thar desert flora - Ummar Iqbal; Hafiza Zahra Naseem; Hadia Jabeen; Muhammad Faraz Gul; Saba Gul; Nargis Naz; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf (The Science of Nature, 2026)

Biochemical Characterization and Phylogenetic Diversity Assessment of Onion (Allium Cepa L.) Genotypes - Samira Habib; Syed Dilnawaz Ahmad Gardezi; Ahmed Mahmoud Ismail; Safira Attacha; Sajid Fiaz; Muhammad Imran Hamza; Armghan Shehzad; Shazia Arif (Plant Molecular Biology Reporter, 2026)

Pharmaco-therapeutic modulation of the Glo1–Nrf2–RAGE functional network in chronic inflammation: polyphenols in the context of current anti-inflammatory therapy - Sajid Ali; Muhammad Saeed Akhtar; Adnan Amin; Atif Ali Khan Khalil; Wajid Zaman (Inflammopharmacology, 2026)

Enhanced estimation of total organic carbon in the longmaxi shale formation using supervised machine learning with lithofacies characterization via K-means clustering - Shaukat Khan; Zhishui Liu; Zhiqiang Lu; Wakeel Hussain; Sohail Ahmed; Muhammad Sajid; Hafiz Hussain Ahmad; Obaidullah; Imdadullah (Carbonates and Evaporites, 2026)

Mesenchymal stem cell-based therapeutic strategies for female infertility: current evidence and emerging targeting approaches - Muhammad Sajid; Faiz-ul Hassan; Atique Ahmed Behan; Fethi Ahmet Ozdemir; Faisal Siddique; Sarfraz Ali Fazlani; Muhammad Asif Arain; Muhammad Saif-ur Rehman (Biotechnology Letters, 2026)

Synergistic biocontrol of Parthenium hysterophorus: the role of Curvularia specifera and Zygogramma bicolorata - Syed Muhammad Ziaullah; Muhammad Hamayun; Amjad Iqbal; Syed Asim; Sajid Ali; Anwar Hussain (Archives of Microbiology, 2026)

Correction to: Structural and functional traits governing the adjustments, survival, and success of C₄ grasses in arid and semi-arid environments - Marwah Saif; Farooq Ahmad; Jazab Shafqat; Ummar Iqbal; Ansa Asghar; Anum Javaid; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Khawaja Shafique Ahmad (Plant and Soil, 2026)

Pharmacological profiling of medicinal plants: a contemporary overview - Bilal Aslam; Muhammad Rehan Sajid; Asif Hussain; Ifraha Abbas (Natural Product Research, 2026)

State-of-the-art adsorbent materials for Bisphenol A removal from water: A systematic evaluation of mechanisms, performance, and environmental sustainability - Muhammad Sajid; Mohammed Altahir Suliman; Mazen K. Nazal; I. Ihsanullah; Naeem Ur Rehman (Journal of Water Process Engineering, 2026)

Acacia (Acacia nilotica) seed oil-based nanoemulsion delays softening of mango fruit by modulating oxidative stress and suppressing cell wall degradation - Shaghef Ejaz; Abdul Manan Abbas; Sajid Ali; Muhammad Azam; Mehdi Maqbool; Muhammad Saqib; Muhammad Abid (Journal of Stored Products Research, 2026)

Radiological contamination in soils near the world's largest rare earth minerals producing region and their impacts on human health: A summary analysis - Amir Hamza; Faisal Khan; Javed Nawab; Junaid Ghani; Sajid Ali; Yaseen Laghari; Luo Xin; Niaz Muhammad; Jing Cui; Zhenggui Wei (Journal of Environmental Radioactivity, 2026)

Amorphous LaAlO3-derived electrolyte: Harnessing structural disorder for high proton conductivity in LT-CFC electrolytes - Muhammad Ahsan Masood; Sajid Rauf; Muhammad Shahid Sharif; Zuhra Tayyab; Naveed Mushtaq; MAK Yousaf Shah; Touseef Ahmad; Atif Nazar; Bushra Bibi; Aljawhara H. Almuqrin; Abdullah N. Alodhayb; Hafsa Mansha; et al. (Fuel, 2026)

Phytochemicals and bioactive properties of mangosteen (Garcinia mangostana L.): A comprehensive review - Ming Yan; Weishi Hou; Huiwen Wang; Ahmet Beyatli; Muhammad Sajid Arshad; Hafiz A.R. Suleria (Food Bioscience, 2026)

Stem Cells and their Key Derivatives in Degenerative Musculoskeletal Diseases - Nawaz Khan; Zeynab Ahmadova; Bin Zeng; Waqas Ahmed; Tayyab Shafiq; Zihao Zhang; Aiyuan Su; Nazim Muhammad; Sajid Khan; Yujie Liang; Li Duan (Stem Cell Reviews and Reports, 2026)

A comprehensive review of the phytochemical, and pharmacological potential of Alnus hirsuta (Spach) Rupr., (Siberian Alder): implications for anti-inflammatory therapeutics - Sajid Ali; Adnan Amin; Muhammad Saeed Akhtar; Khizar Abdullah Khan; Ishaq N. Khan; Imran Khan; Wajid Zaman; Atif Ali Khan Khalil (Inflammopharmacology, 2026)

Rock–water interactions in the coal mining area of Dukki, Balochistan, determine the drinking and irrigation suitability of groundwater: an in-depth risk assessment - Ghazala Mohammad Ali; Muhammad Akhtar; Muhammad Faraz Bhatti; Fazal Adnan; Malik Badshah; Ghayas Haider Sajid; Ghulam Haider (Environmental Geochemistry and Health, 2026)

Surveillance of citrus canker: a threat to Pakistani citrus industry-status and distribution of citrus canker in major citrus growing regions of Pakistan - Safi Ullah; Zia ur Rehman; Muhammad Tayyab; Aamir Iqbal; Abdullah Jalal; Jinbiao Ma; Muhammad Awais; Sajid Ali (Journal of Plant Pathology, 2026)

Evaluation of lead bioaccumulation potential in freshwater snail species as indicators of aquatic pollution in lentic and lotic waterbodies of Sargodha, Pakistan - Ayesha Tariq; Rana Muhammad Ahsan Sajid; Naunain Mehmood; Aima Iram Batool; Hira Muqaddas; Zafar Iqbal Khan (Environmental Monitoring and Assessment, 2026)

Structural and functional traits governing the adjustments, survival, and success of C₄ grasses in arid and semi-arid environments - Marwah Saif; Farooq Ahmad; Jazab Shafqat; Ummar Iqbal; Ansa Asghar; Anum Javaid; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Khawaja Shafique Ahmad (Plant and Soil, 2026)

Unraveling oak diversity: molecular characterization and phylogenetic relationships of Quercus species from the western Himalayas - Ayesha Azeem; Daniel Potter; Abdul Majid; Sajjad Sajjad; Khushi Muhammad; Irfan Ullah; Asif Khan; Abdulwahed Fahad Alrefaei; Sajid Ali (Plant Systematics and Evolution, 2026)

Synthesis and integrative multimodal evaluation of cholic acid-based hydrazone conjugates: in vitro, in silico, and in vivo studies - Muhammad Hassan Butt; Kanwal Rehman; Shagufta Kamal; Muhammad Sajid Hamid Akash (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Stage-specific endophytic colonization of maize by Metarhizium anisopliae (Clavicipitaceae, Hypocreales): effects on Spodoptera Frugiperda (Smith, 1797) (Lepidoptera: Noctuidae) fitness and plant growth - Muhammad Adnan; Muhammad Irfan Ullah; Muhammad Arshad; Emaan Sajid; Lamya Ahmed Alkeridis; Laila A. Al-Shuraym; Ohud Muslat Aharthy; Seham Sater Alhelaify; Hosny Kesba; Samy Sayed (Journal of Plant Diseases and Protection, 2026)

Assessing Genetic Variation and Population Connectivity in Wallago attu: A Call for Enhanced Conservation Measures - Taqwa Safdar; Khalid Abbas; Cedric Gondro; Sajid Abdullah; Muhammad Anjum Zia (Biochemical Genetics, 2026)

Effective removal of lamotrigine using colloidal activated carbon - Abdullah Basaleh; Mohammed Benaafi; Shehzada Muhammad Sajid Jillani; Shahd Alghamdi; Bassam Tawabini (Chemosphere, 2026)

Hydro-structural response of filled vs. not-filled monopiles for large offshore wind turbines under operational and extreme load conditions - Sajid Ali; Muhammad Waleed; Daeyong Lee (Ocean Engineering, 2026)

Facile synthesis and photocatalytic performance of Mn-Doped CeO2 composites for visible-light-driven degradation of methylene blue and tetracycline - Zahoor Ahmad; Alamgir; Muhammad Arfan; Sajid Ali; Aqsa Asrar; Cheng Xu; Aung Ko Ko Kyaw; Zhenlun Song (Journal of Water Process Engineering, 2026)

Oligochitosan coating preserves quality of fresh table grapes by modulating γ-aminobutyric acid metabolism and antioxidant system activity under two temperature regimes - Muhammad Hassan; Sajid Ali (Journal of Stored Products Research, 2026)

Integrated ADME, metabolomics, and multi-target docking of Novel methoxy- and thiophene-substituted benzodioxane hydrazones - Aisha Rafique; Kanwal Rehman; Shagufta Kamal; Muhammad Sajid Hamid Akash (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Climate-driven Modifications in Structural and Functional Traits of Couch Grass [Cynodon Dactylon (L.) Pers.] along Elevation Gradient - Sana Fatima; Farooq Ahmad; Zahida Parveen; Sana Basharat; Mansoor Hameed; Ansa Asghar; Muhammad Sajid Aqeel Ahmad; Majid Anwar; Syed Mohsan Raza Shah; Raza Shah; Muhammad Ashraf; Muhammad Kaleem; et al. (Journal of Soil Science and Plant Nutrition, 2026)

Integrating phenotypic, antioxidant, and molecular analyses to identify drought-tolerant wheat genotypes for climate resilience and genetic improvement - Hafiz Ghulam Muhu Din Ahmed; Tao Yang; Mueen Alam Khan; Muhammad Irfan Akram; Rashid Iqbal; Sajid Hussain; Muhammad Danial Shafiq; Mohamed El-Zaidy; Islem Abid (Cereal Research Communications, 2026)

Evaluation of leaf extracts of Moringa oleifera Lam. On testosterone enanthate-induced polycystic ovary syndrome (PCOS) in mice - Shakeela Khalid; Muhammad Arshad; Farzana Siddque; Muhammad Sajid Arshad; Marina Sajid; Waseem Khalid; Zaira Aziz; Muhammad Zubair Khalid; Sulaiman Ali Alharbi; Mohammad Javed Ansari; Abdellah Zinedine; Elena Bartkiene; et al. (Advances in Traditional Medicine, 2026)
Polycystic ovary syndrome (PCOS) is a multifactorial endocrinological and metabolic disorder that affects women of reproductive age. It is often associated with hyperandrogenism, obesity, anovulation, infertility and insulin resistance. In this study, the imminent efficacy of MoLP ( Moringa oleifera leaf powder) and MoLE ( M. oleifera leaf extract) in treating PCOS in female albino mice was explored. Female albino mice were injected with testosterone enanthate [1.0 mg/100 g body weight (b.w.)] for 35-days to induce PCOS. For the treatment, mice were administered with M. oleifera leaf powder (250 and 500 mg/kg b.w.), M. oleifera leaf extract (250 and 500 mg/kg b.w.), and metformin (250 mg/kg b.w.) for 14 days. Following the intervention, body weight, blood glucose, c-peptide, testosterone, follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels and stages of the estrus cycle were measured at 0, 7 and 14 days. The ovaries were examined stereologically to determine the number and diameter of follicles. Results indicated that MoLP, MoLE (500 mg/kg b.w.) and metformin (250 mg/kg b.w.) significantly decreased body weight, blood glucose, c-peptide, testosterone and LH levels while increasing FSH levels and ovary weight over time compared to PCOS-induced mice. Additionally, regulation of the estrus cycle and folliculogenesis in PCOS-induced mice was observed. Overall, the present study revealed that M. oleifera may have the potential as a therapeutic intervention for PCOS. Graphical Abstract

Trait dynamics of endemic Festuca species reveal cold-resilience across elevation gradient - Khawaja Shafique Ahmad; Syed Mohsan Raza Shah; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Ummar Iqbal; Ansar Mehmood; Sana Fatima; Wisal Muhammad Khan; Muhammad Ashraf; Hazem M. Kalaji; Manzer H. Siddiqui (Acta Physiologiae Plantarum, 2026)

PFAS-driven modulation of algal organic matter enhances dissolved organic matter reactivity and disinfection by-product formation: Mechanistic elucidation via multi-spectroscopic analysis, and mitigation by coagulation and nanofiltration - Mian Jawaduddin; Zhaoyang Su; Sajid Rashid; Muhammad Saboor Siddique; Nigel Graham; Wenzheng Yu (Journal of Hazardous Materials, 2026)

Novel Styrofoam-sludge biochar for Pb and Zn adsorption: Bioavailability and reduction in maize-cultivated contaminated soils - Muhammad Ubaid Ali; Mehr Ahmed Mujtaba Munir; Ruilian Yu; Gongren Hu; Balal Yousaf; Sajid Ali; Muhammad Adnan; Cheng Liping; Xiangliang Pan; Ming Hung Wong (Journal of Cleaner Production, 2026)

Synergistic effects in FeP4-NPC-CP Nanocomposites electrocatalysts for Boosted nitrate reduction to ammonia - Ya-Fei Guo; Sajid Mahmood; Anum Bilal; Ali Bahadur; Shahid Iqbal; Ali Hussain; Muhammad Sajjad; Syed Kashif Ali; Salah Knani (Fuel, 2026)

Disordered Pr-alumina: Enabling fast proton dynamics across energy systems - Hafsa Mansha; Touseef Ahmad; Kashf Zaman; Sajid Rauf; Muhammad Khalid; M.Ahsan Masood; Shahzad Rasool; Atif Nazar; Bushra Bibi; Nawal K. Almaymoni; Yuzheng Lu; Jun Wang; et al. (Fuel, 2026)

Root microstructural traits regulate ion homeostasis in bush morning glory (Ipomoea carnea Jacq.) for invasiveness success in saline environments - Syed Mohsan Raza Shah; Naila Hadayat; Jazab Shafqat; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Farooq Ahmad; Maham Zia; Zaheer Abbas; Zahida Parveen; Muhammad Ashraf; Ummar Iqbal; Ansa Asghar; et al. (The Science of Nature, 2026)

Integrative biochemical and computational evaluation of methyl eugenol, naphthalene, and linalool as natural multitarget therapeutics for smoking cessation-related metabolic disturbances - Mahpara Gondal; Muhammad Sajid Hamid Akash; Shagufta Kamal; Kanwal Rehman (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Metabolomic and biochemical evaluation of linalool and methyl eugenol as natural alternatives to varenicline in nicotine-induced metabolic dysfunction - Mahpara Gondal; Muhammad Sajid Hamid Akash; Shagufta Kamal; Kanwal Rehman (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Spatiotemporal dynamics of a reaction-diffusion nutrient-algae model - Muhammad Waqas Yasin; Mobeen Akhtar; Moutaz Alazab; Mustafa Inc; Zafarullah Baber; Muhammad Sajid Iqbal; Shahram Rezapour (Modeling Earth Systems and Environment, 2026)

Antibacterial Activity of Anthraquinones Isolated from Reynoutria Japonica Against Staphylococcus aureus: An in Silico and In Vitro Approach - Iqra Anam Khawaja; Sajid Ali; Muhammad Faheem; Syed Babar Jamal; Adnan Haider; Falak Niaz; Mi-Jeong Ahn; Mutiullah Khattak; Atif Ali Khan Khalil (Journal of Pharmaceutical Innovation, 2026)

A review on integrated isotopic and receptor model approaches for urban REE source appointment - Muhammad Ubaid Ali; Muhammad Adnan; Xiao Yan Lin; Sajid Ali; Zhuanxi Luo; Yu Yan; Gongren Hu; Ruilian Yu; Ming Hung Wong (Environmental Geochemistry and Health, 2026)

The triple threat: the interwoven impact of climate vulnerability, income Inequality, and gender parity on educational access and outcomes - Samina Zamir; Muhammad Sajid Mehmood; Babar Nawaz Abbasi; Zhencun Wang (Environment, Development and Sustainability, 2026)

Tailoring of Cerium Oxide Nanosheets Having Superior Peroxidase Catalytic Activity for Colorimetric Detection of Hydrogen Peroxide - Mohib Ullah; Muhammad Aslam Khan; Sajid Ali; Asfandyar; Zeeshan Tahir; Muhammad Babar Saeed; Vineet Tirth; Ali Algahtani; Ruqia Nazir; Muslim Khan (Journal of Fluorescence, 2026)

Impact of Aspergillus flavus infection on nutrient composition and storage quality of maize (Zea mays L.) using side needle inoculation - Imran Manzoor; Muhammad Arshad; Rao Muhammad Samran Gul; Ijaz Rasool Noorka; Momina Hussain; Muhammad Sajid; Noorah A. AlKubaisi; Sezai Ercisli; Mohamed S. Elshikh; Abdul Waheed (Journal of Stored Products Research, 2026)

Synthesis and characterization of indole-3-butyric acid-based hydrazones: from multifunctional enzyme inhibition to therapeutic potential for drug development - Sehar Madni; Muhammad Sajid Hamid Akash; Shagufta Kamal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Multi-scale debris flow risk assessment using morphometrics in high-altitude catchments of Northern Pakistan - Yaseen Ullah; Muhammad Shafique; Nisar Ali Shah; Ghazanfar Ali Khattak; Sajid Ullah (Natural Hazards, 2026)

Natural products in medicinal chemistry: targeting inflammatory pathways with plant-derived compounds - Adnan Amin; Muhammad Saeed Akhtar; Atif Ali Khan Khalil; Sajid Ali; Wajid Zaman (Medicinal Chemistry Research, 2026)

Seed Priming with Osmolytes Ameliorates Salinity Tolerance in Maize (Zea mays L.) Through Embryonic Modifications - Paris Riaz; Ansa Asghar; Sana Fatima; Sana Basharat; Zahida Parveen; Mansoor Hameed; Farooq Ahmad; M. Sajid Aqeel Ahmad; Muhammad Ashraf; Faakeha Islam; Syed Mohsan Raza Shah; Qasim Ali (Journal of Plant Growth Regulation, 2026)

Anti-arthritic appraisal of Acorus calamus L. extracts in complete Freund’s adjuvant‑induced arthritic Wistar rats via regulating inflammatory cytokines and OPG/RANKL pathway - Muhammad Usman Bari; Asif Hussain; Bilal Aslam; Zia-ud-Din Sindhu; Muhammad Rehan Sajid; Rifat Ullah Khan (Inflammopharmacology, 2026)

Impact of Thermal Damage on the Physical and Mechanical Properties of Carbonate Rocks - Subhan Ullah; Muhammad Sajid; Khalid Latif; Abdul Rahim Asif; Muhammad Rizwan (Geotechnical and Geological Engineering, 2026)

Aspergillus Welwitschiae Regulates Response of Wheat at Multiple Levels To Alleviate Induced Chromate Stress - Urooj Jamal; Zia Ur Rahman; Muhammad Qadir; Muhammad Hamayun; Sajid Ali; Anwar Hussain (Current Microbiology, 2026)

Cardiometabolic Dysregulation and PON1 Genetic Susceptibility in Chronic E-waste Recyclers Exposed to Potentially Toxic Elements - Aneela Shoukat; Syed Muhammad Nurulain; Rashid Nazir Qureshi; Amina Zafar; Sabir Hussain; Sosan Andleeb Khan; Sajid Mehmood; Sadia Asmat; Saqlain Raza; Syed Tahir Abbas Shah (Cardiovascular Toxicology, 2026)

Characteristics and evaluation of E2S member of Sanduo formation of Gaoyou Sag, North Jiangsu Basin, China - Orkhan Isgandarov; Yang Shaochun; Muhammad Kashif; Aynur Abdullayeva; Muhammad Sajid; Nasib Efandi; Muhammad Ahmed (Arabian Journal of Geosciences, 2026)

Innovative Fe-F-Co-doped NiO nanoarrays: Pioneering high-efficiency electrochemical nitrate reduction to ammonia - Anum Bilal; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Ibrahim Khan; Imran Mahmood Khan; Muhammad Sajjad; Shahid Ali; Nicholas M. Musyoka; Guocong Liu; Abd-ElAziem Farouk; Nouf M. Alyami (Journal of Environmental Chemical Engineering, 2025)

Ecological resilience of Gallon's curse (Cenchrus biflorus Roxb.) in hyperarid and hypersaline environments - Sana Basharat; Farooq Ahmad; Mansoor Hameed; Zahida Parveen; Muhammad Sajid Aqeel Ahmad; Muhammad Waseem; Ansa Asghar; Sana Fatima; Liu Pingwu; Mehwish Noor; Syed Mohsan Raza Shah; Muhammad Ashraf (Journal of Arid Environments, 2025)

Retraction notice to “Citric acid-capped NiWO4/Bi2S3 and rGO-doped NiWO4/Bi2S3 nanoarchitectures for photocatalytic decontamination of emerging pollutants from the aqueous environment” [Environ. Res. Volume 212, Part B, September 2022, 113276] - Hina Liaquat; Muhammad Imran; Shoomaila Latif; Sajid Iqbal; Nazim Hussain; Muhammad Bilal (Environmental Research, 2025)

One-pot Facile Synthesis of Polyhexahydrotriazine and Investigating its Application for Removal of N-Nitrosodiphenylamine from Wastewater - Yasir Abbas; Muhammad Sajid; Durga Rao Gijjapu; Mazen K. Nazal (Water, Air, & Soil Pollution, 2025)

Reactive oxygen species production and signal transduction in response to stress triggered by Alternaria elicitors in Brassicaceae - Sana Munir; Ahmad N. Shahzad; Avanish Rai; Veselin Petrov; Tsanko Gechev; Sajid Shokat; Muhammad K. Qureshi (Plant Molecular Biology, 2025)

Hybrid ensembled machine learning algorithm for landslide susceptibility assessment and data enhancement via Dual Discriminator Conditional Generative Adversarial Network - Sajid Hussain; Bin Pan; Wajid Hussain; Meer Muhammad Sajjad; Muhammad Ali; Zeeshan Afzal; Rebouh Nazih Yacer; Aqil Tariq (Natural Hazards, 2025)

Beta-Glucan in barley as a natural immunomodulator: mechanisms and therapeutic potential - Hafiz Ghulam Muhu Din Ahmed; Li’E Yang; Xiaomeng Yang; Jiazhen Yang; Sajid Hussain; Muhammad Danial Shafiq; Muhammad Irfan Akram; Muhammad Sajad; Yawen Zeng (Molecular Biology Reports, 2025)

Exploring the therapeutic potential of Nasturtium microphyllum (Boenn.) Rchb.: a combined in-vitro, in-vivo and in-silico approach - Rabia Khan; Muhammad Musa; Syed Mubassir Shah; Hussan Ara Begum; Alaa S. Alhegaili; Sajid Hussain; Atif Ali Khan Khalil; Sajid Ali (Inflammopharmacology, 2025)

Prediction of RNA editing sites and genome-wide characterization and identification of PERK gene family in Oryza sativa in response to salinity stress - Hafiz Muhammad Waqas; Muhammad Abu Bakar Saddique; Sajid Fiaz; Afnan A. Alnufaei; Muhammad Ali Sher; Badr Alharthi; Muhammad Hammad Nadeem Tahir; Mahmood Alam Khan; Shahmeer Shahid; Seung Hwan Yang (Genetic Resources and Crop Evolution, 2025)

Harnessing breeding and biotechnological innovations for global food security under climate change - Obaid Ur Rehman; Feifei Zhu; Xinjuan Hu; Xiangru Xu; Muhammad Uzair; Jiangya Qian; Sajid Fiaz; Shuhao Huo (Functional & Integrative Genomics, 2025)

Transgenic AVP1 wheat (Triticum aestivum L.) inoculated with plant growth-promoting Azospirillum strains improves biomass and grain yield - Muhammad Sajid; Tahir Naqqash; Muhammad Arshad; Tawaf Ali Shah; Turki M. Dawoud; Mohammed Bourhia; Imran Habib (Cereal Research Communications, 2025)

Integrating hematological profile and biomarker analysis for metals and metalloids ecotoxicological assessment on Wallago catfish and Indian carp health in Head Siphon, Mailsi, Pakistan - Kaynat Saeed; Sajid Abdullah; Muhammad Yaqoob; Minahal Fatima; Zunaira Majeed; Muhammad Ismail; Sara F. Ghanem; Moaheda E.H. Eissa; Hesham Hassanien; Zulhisyam Abdul Kari; El-Sayed Hemdan Eissa (BioMetals, 2025)

A Multivariate AI-Driven Generalized Framework for Structural Load Prediction of Monopile Used for Offshore Wind Turbines Under Non-Linear Wind and Wave Conditions - Sajid Ali; Muhammad Hassaan Farooq Khan; Daeyong Lee (Journal of Marine Science and Engineering, 2025)
Predicting structural loads on offshore wind turbine support structures under varying environmental conditions is a complex yet critical task, particularly for large-capacity turbines such as the 15 MW offshore wind turbine. Current prediction methods often struggle with accuracy, especially for torsional moments, due to the non-linear interactions between wind parameters and structural responses. To address this challenge, present study develops a generalized load estimation framework using multivariable polynomial regression, leveraging 10,000 numerical simulations. The framework accounts for four critical variables: Extreme Wind Speed (30 to 40 m/s), Turbulence Intensity (12% to 16%), Flow Inclination Angle (−8° to +8°), and Shear Exponent (0.1 to 0.3). The proposed equations predict six key moment components at the tower base, including the bending moments about the y-axis, torsional moments about the z-axis, bending moments in the x-y, x-z, and y-z planes, and the resultant combined moment. The framework was validated using 2000 testing data points, achieving high accuracy with R2 values exceeding 0.92 for all moments. Specifically, the prediction accuracy was highest for the resultant combined moment and y-z bending moment, with average absolute errors of 5.76% and 5.97%, respectively, while x-z bending moment had a slightly higher error of 13.91%, highlighting that torsional moments are inherently more challenging to predict. Heatmap and scatter plot analyses confirmed that the predicted moments align closely with the simulated values, particularly for the torsional moment about the z-axis and y-z bending moment, with standard deviation values as low as 4.85. By optimizing polynomial degrees between 2 and 4, the framework effectively balances prediction accuracy and computational efficiency. This approach provides engineers and scientists with a reliable tool for load estimation, facilitating improved design and analysis of offshore wind turbine support structures.

Magnetic MOF-Based Immunosensing Strategy with Quantum Dot Labeling for Efficient Electro-chemiluminescent Detection of Alpha-fetoprotein - Mariyam Fatima; Muhammad Faizan; Iqra Jabeen; Muhammad Fiaz; Ansar Ali; Syed Kashif Ali; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Ibrahim Jafri; Abd-ElAziem Farouk (Journal of Fluorescence, 2025)

Strategic valorization of heterogeneous organic wastes for sustainable food packaging: A circular economy approach - Shumaila Masood; Hafiz Muhammad Shahbaz; Md. Abdus Salam Shaik; Sajid Maqsood (Trends in Food Science & Technology, 2025)

Modulating the support layer for the fabrication of high flux nanofiltration membrane and its application in desalination and micropollutants’ rejection - Elham Saud Alkhulaify; Shehzada Muhammad Sajid Jillani; Hassan Younas; Saheed A. Ganiyu; Khalid Alhooshani (Journal of Environmental Management, 2025)

Recent advancements in UiO-66(Zr) MOFs and their derivatives: Designing water-stable membranes for water applications - Yahaya A. Muhammad; Muhammad Sajid; Abubakar Umar; Niaz Ali Khan; Ismail Abdulazeez; Billel Salhi; Nadeem Baig; Wail Falath (Desalination, 2025)

Photo-activated proton-incorporation into Nd-aluminum for superionic conductors - Atif Nazar; Bushra Bibi; Sajid Rauf; Rizwan Raza; Muhammad Farrukh Sarfraz; Muhammad Khalid; Muhammad Faisal Anwar; Muhammad Ahsan Masood; Kashif Nazar; Syed Asad Abbas Bukhari; Khuloud A. Alibrahim; Bin Zhu; et al. (Chemical Engineering Journal, 2025)

Evaluation of repellent and contact toxic effects of Citrullus colocynthis against the Periplaneta americana - Adeena Malik; Khalid Mehmood; Muhammad Sajid Nadeem (International Journal of Tropical Insect Science, 2025)

Xanthan gum coating delays ripening of harvested mango (Mangifera indica L.) fruit by suppressing chlorophyll catabolism and cell wall polysaccharides degradation - Maimona Qasim; Sajid Ali; Hafiz Umer Javed; Safina Naz; Ahmad Sattar Khan; Muhammad Hassan; Rana Naveed Ur Rehman (Postharvest Biology and Technology, 2025)

Ultrahigh-porosity peony-like magnesium oxide for the superior adsorption of arsenic (III) and arsenic (V) from aqueous solutions - Ghulam Asghar; Duc Anh Nguyen; Thi Hai Chau Dong; Sumaira Manzoor; Shahid Ali; Muhammad Mansha; Shehzada Muhammad Sajid Jillani; Safyan Akram Khan (Journal of Hazardous Materials, 2025)

Tailoring the local environment of biochar by synergistic effects of AuPd alloy for enhanced catalytic wet air oxidation of formaldehyde - Sajid Ali; Kok Bing Tan; Kaiji Xu; Songbo Chen; Muhammad Ubaid Ali; Amad Arshad; Shafqat Ullah; Shamaila Sajjad; Andriambinintsoa Ranaivoson Tojonirina; Guowu Zhan (Journal of Environmental Chemical Engineering, 2025)

Prediction of water status during freeze drying with genetic and whale algorithms of machine learning - Shoaib Younas; Muhammad Ahmad; Ukasha Arqam; Muhammad Sajid Manzoor; Xin Wang; Weijie Li; Caiyun Liu; Zeshan Ali; Muhammad Azeem Sabir; Muhammad Imran (International Journal of Refrigeration, 2025)

Preventing electrolyte degradation through enhanced MnO2 deposition/dissolution in Zn−MnO2 battery using vanadium redox mediator - Mohsin Ali; Xinhua Zheng; Ruihao Luo; Muhammad Sajid; Saba Hazoor; Touqeer Ahmad; Aoun Raza; Nawab Ali Khan; Mingjie Wu; Wei Chen (Chemical Engineering Journal, 2025)

The generative adversarial neural network with multi-layers stack ensemble hybrid model for landslide prediction in case of training sample imbalance - Wajid Hussain; Hong Shu; Hasnain Abbas; Sajid Hussain; Isma Kulsoom; Saqib Hussain; Hajra Mustafa; Aftab Ahmed Khan; Muhammad Ismail; Javed Iqbal (Stochastic Environmental Research and Risk Assessment, 2025)

Evaluating the preclinical efficacy of naringenin in rheumatoid arthritis: a meta-analysis of in vivo studies - Muhammad Muzammil Nazir; Ayesha Batool; Muhammad Asad Sajid; Asma Ashraf (Inflammopharmacology, 2025)

Thermal Thresholds and Mechanical Behavior of Granitic Rocks from Northern Pakistan: Implications for Rock Engineering - Abdul Rahim Asif; Muhammad Sajid; Waqas Ahmed; Ihtisham Islam; Abid Nawaz; Salman Ahmed Khattak (Geotechnical and Geological Engineering, 2025)

Comprehensive ampelographic and biochemical profiling of exotic grapevine (Vitis vinifera L.) cultivars grown under semi-arid conditions - Ubaid Abdul Khaliq; Irfan Ali; Abdel‑Halim Ghazy; Muhammad Tahir Akram; Mahmood-ul-Hassan; Haider Ali; Umer Habib; Tanveer Hussain; Kotb A. Attia; Sajid Fiaz; Abdullah A. Al-Doss; Muhammad Uzair; et al. (Genetic Resources and Crop Evolution, 2025)

Preliminary Detection of Bats-associated Influenza A virus from Pakistan - Sidra Rahman; Syed Ahsan Shahid; Hassan Ayaz; Sajid Ali Shah; Muhammad Ali (Current Microbiology, 2025)

Comprehensive Molecular Profiling of AcrAB-TolC Efflux Pump Genes in Salmonella typhi Isolates from Typhoid Infected Patients - Muhammad; Sadiq Azam; Noor Rehman; Alaa S. Alhegaili; Ibrar Khan; Aakash Ahmad; Atif Ali Khan Khalil; Sajid Ali (Current Microbiology, 2025)

Urban walkability assessment: methods and implications for city planning - Hamza Chaudhary; Shakeel Mahmood; Yuping Su; Muhammad Sajid Mehmood; Muhammad Irfan Ahamad (Environment, Development and Sustainability, 2025)

Green technology for radioactive waste treatment: Bio membrane perspective - Muhammad Yusuf; Shehzada Muhammad Sajid Jillani; Farid Fadhillah; Pieter David Boom; Isam H. Aljundi; Afaque Shams (Chemosphere, 2025)

Integrated PSInSAR and SBAS-InSAR analysis for landslide detection and monitoring - Sajid Hussain; Bin Pan; Wajid Hussain; Meer Muhammad Sajjad; Muhammad Ali; Zeeshan Afzal; M. Abdullah-Al-Wadud; Aqil Tariq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Nano-engineered biochar enhances soil microbial interactions and maize transcriptomic pathways for cadmium detoxification - Muhammad Umair Yasin; Sajid Muhammad; Nana Chen; Fakhir Hannan; Muhammad Afzal; Zulqarnain Haider; Bahar Ali; Irshan Ahmad; Muhammad Rehman; Yinbo Gan (Journal of Hazardous Materials, 2025)

Polyethylene Glycol Mitigates Cadmium Toxicity in Raphanus sativus L. by Regulating Enzymatic and Nonenzymatic Antioxidant Defence Mechanisms - Muhammad Sajid; Shakil Ahmed; Rehana Sardar; Nasim Ahmad Yasin (Journal of Soil Science and Plant Nutrition, 2025)

Do financial inclusion and green growth matter for environmental sustainability? A fresh insight through nonlinear model - Muhammad Sajid; Muhammad Akbar Ali Ansari; Arsalan Tanveer; Noreen Safdar; Muhammad Faheem (Clean Technologies and Environmental Policy, 2025)

The digital solution: how artificial intelligence is revolutionizing energy poverty alleviation - Zhang Tianyi; Qili Zhou; Sajid Ali; Raima Nazar; Muhammad Khalid Anser (Environment, Development and Sustainability, 2025)

Kojic acid suppresses browning incidence, maintains quality and sensory attributes of harvested loquat fruit by upregulating enzymatic and non-enzymatic antioxidants - Saqib Ayyub; Ahmad Sattar Khan; Raheel Anwar; Abdul Rehman; Hafiz Muhammad Shoaib Shah; Sajid Ali (Postharvest Biology and Technology, 2025)

Molecular identification, risk factors’ assessment and phylogenetic analysis of Toxoplasma gondii in goats from Malakand Division, Khyber Pakhtunkhwa, Pakistan - Ahmad Irshad; Shumaila Noreen; Uswa Sajid; Muhsin Jamal; Muhammad Anwar Iqbal; Ubaid Ullah; Talat Sabtain; Shakir Ullah; Eliana Ibañez-Arancibia; Patricio R. De Los Ríos-Escalante; Hanène Belkahia; Mourad Ben Said; et al. (Veterinary Research Communications, 2025)

Evaluating the impacts of environmental stresses on agriculture in the context of climate resilience - Muhammad Arif; Sajid Fiaz; W. M. W. W. Kandegama; Sujitraj Sheth; Luhua Li (Plant Molecular Biology, 2025)

Green and cost-effective photocatalytic degradation of murexide dye with acid catalyst - Zain Ul Abidin; Adnan Majeed; Muhammad Adnan Iqbal; Muhammad Kashif; Tabinda Fatima; Muhammad Yousif; Muhammad Arbaz; Syed Arslan Hussain; Muhammad Sajid (Clean Technologies and Environmental Policy, 2025)

Genetic analysis in a consanguineous MCPH family revealed a refinement of the MCPH12 locus and a founder effect of the recurrent CDK6 variant [c.589G>A, p.(Ala197Thr)] in the Pakistani population - Muzammil Ahmad Khan; Jasmin Blatterer; Markus Kuster; Lukas Kaufmann; Peter M. Kroisel; John B. Vincent; Muhammad Zubair; Muhammad Muzammal; Nisar Ahmad; Shakil Abbas; Wasim Shah; Muhammad Zeeshan Ali; et al. (Journal of Genetics, 2025)

Gum Arabic Organic Coating Maintains Freshness and Modulates Oxidative Stress by Augmenting the Antioxidant Activities of Harvested Ber Fruit - Alisha Noor; Ahmad Sattar Khan; Raheel Anwar; Sajid Ali; Rana Naveed Ur Rehman; Saqib Ayyub; Muhammad Haider Ali (Applied Fruit Science, 2025)

Inconsistencies in stratigraphic interpretation and correlation – Comments on “depositional cyclicity of lower Cambrian strata in the NW Himalayas: Regional sequence stratigraphy of the Indian passive margin” by Mahmood et al. (2024) - Malik Muhammad Saud Sajid Khan; Bing Pan; Maoyan Zhu (Marine and Petroleum Geology, 2025)

A critical review of opportunities and challenges of solid waste management in an emerging economy- evidence from Pakistan - Sajid Rashid; Hameeda Sultan; Wajid Rashid; Bushra Danish Talpur; Roberto Xavier Supe Tulcan; Muhammad Tariq Khan; Eve Bohnett; Muhammad Safar Korai; Lixiao Zhang (Environmental Development, 2025)

Cadmium Toxicity Affects Morpho-Physiological and Biochemical Attributes in Gladiolus grandiflorus L.: The Mitigating Roles of Exogenous Strigolactone (GR24) - Muhammad Ahsan; Muhammad Abdullah; Emanuele Radicetti; Mohamed Farouk Elsadek; Ali Bakhsh; Mateen Sajid; Mohammad Valipour; Aftab Jamal; Hera Gul; Syed Mohsin Abbas (Water, Air, & Soil Pollution, 2025)

Adaptive response of rare mountain sedge (Carex Ecostata C.B. Clarke) to hyper-cold environments - Ansa Asghar; Amina Ameer; Farooq Ahmad; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Mingzhou Qin; Asima Asghar; Shahid Ali Khan; Hao Yang Li; Zhan Fei Zhang (Plant and Soil, 2025)

Marine life as a source of anti-prostate cancer agents: an updated overview (2003–2023) - Amjad Hussain; Ammara Sohail; Muhammad Sajid Hamid Akash; Sarosh Iqbal; Kanwal Rehman; Muhammad Imran; Shoaib Khan; Muhammad Adnan Ayub; Daijie Wang; Dildar Ahmed; Mohammed Hadi Ali Al-Jumaili; Maria Bashir; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Probabilistic seismic loss estimation for residential buildings in Pakistan - Sajid Mehmood; Zainulabideen Ali Khan; Fawad Ahmed Najam; Muhammad Usman (Natural Hazards, 2025)

Health risks associated with occupational contaminants of heavy metals across different professions - Sosan Andleeb Khan; Syed Muhammad Nurulain; Baseet Haroon Khan; Aneela Shoukat; Sajid Mehmood; Rabeet Haroon Khan; Rashid Nazir Qureshi; Amina Zafar; Ammara Younas; Syed Tahir Abbas Shah (Environmental Geochemistry and Health, 2025)

Structural and functional traits driving Chloris flagellifera proliferation in arid saline environments - Ummar Iqbal; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Khawaja Shafique Ahmad; Ansar Mehmood; Nargis Naz; Muhammad Akram (Acta Physiologiae Plantarum, 2025)

Development and techno-economic analysis of an innovative solar-based ammonia synthesis system - Zihan Lin; Muhammad Sajid Khan; Saboora Khatoon; Shuiqing Zhou; Weiya Jin; Muhammad Abid; Syed Waqas Hussain Shah; Chen Chen; Ali Ahmed Alqahtani (Process Safety and Environmental Protection, 2025)

Petrogenesis and tectonic implications of Paleozoic S-type granitic gneisses of Nanga Parbat Syntaxis, North Pakistan - Amjad Hussain; Kui-Dong Zhao; Delores M. Robinson; Sakine Moradi; Muhammad Sajid; Hafiz U. Rehman; Qian Li; Syed Mumtaz Hussain; Rahat Ali; Syed Asim Hussain (Lithos, 2025)

Spatio-temporal distribution, diet and human conflict of snow leopard (Panthera uncia) in the Khunjerab National Park, Gilgit Baltistan - Saira Akber; Tariq Mahmood; Tahir Mehmood; Amjad Rashid Kayani; Muhammad Sajid Nadeem; Faraz Akrim (Food Webs, 2025)

Integrated Application of Drought-Tolerant Phosphate Solubilizing Bacteria and Native P Source Improves P Availability with Sustainable Wheat Production - Hafiz Shahid Hussain; Saira Tabbasum; Naima Mahreen; Mahreen Yahya; Khansa Ejaz; Zoya Aslam; Muhammad Imtiaz; Ejaz ul Islam; Zahid Iqbal Sajid; Sumera Yasmin (Journal of Soil Science and Plant Nutrition, 2025)

Synergistic Application of Biochar and Bio-Organic Phosphate Enhances Drought Tolerance in Maize by Modulating Antioxidant Defense and Reducing Oxidative Stress - Ghulam Sarwar; Zainab Zahra; Tauseef Anwar; Huma Qureshi; Faizan Khalid; Muhammad Waqar Hassan; Muhammad Younus; Muhammad Sajid-ur-Rehman; Huma Rao; Faisal Shahzad; Wajid Zaman; Mansour Shrahili; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Amendment of Tomato (Lycopersicon esculentum L.) Grown in Calcareous Soil with Spent Mushroom Substrate-derived Biochar: Improvement of Morphological, Biochemical, Qualitative Attributes, and Antioxidant Activities - Hasan Sardar; Muhammad Waqas; Aamir Nawaz; Safina Naz; Sajid Ali; Shaghef Ejaz; Riaz Ahmad; Ayman A. Ghfar; Saikh M. Wabaidur; Sami Abou Fayssal (Journal of Soil Science and Plant Nutrition, 2025)

Mechanistic Insights into Pressmud-Mediated Improvement in Wheat Growth, Quality and Productivity under Lead Contaminated Salt-Affected Soil - Basit Haider; Muhammad Imran; Muhammad Ashraf; Sajid Mahmood (Journal of Soil Science and Plant Nutrition, 2025)

Correction: Exploration of molecular interactions responsible for anti-inflammatory attributes of GI friendly micro-sized formulation of flurbiprofen and clove oil - Hafiz Muhammad Zubair; Mohamed Farouk Elsadek; Sajid Asghar; Khalid S. Al-Numair; Malik Saadullah; Shafqat Rasul Chaudhry; Thomas Efferth; Muhammad Asif (Inflammopharmacology, 2025)

Genome-wide identification and characterization of light-responsive FAR1 gene family in finger millet (Eleusine coracana) under abiotic stress - Urooba Abid; Azhar Iqbal; Mahnoor Mazher; Shabana Bibi; Sara Ashraf; Mohamed Kamel; Ghadeer M. Albadrani; Muath Q. Al-Ghadi; Mohamed M. Abdel-Daim; Muhammad Sajid (Genetic Resources and Crop Evolution, 2025)

Impact of petrographic and physico-mechanical properties on aggregate suitability of the early Devonian Nowshera formation: a case study from the Peshawar Basin, Pakistan - Abid Nawaz; Muhammad Sajid; Waqas Ahmed; Abdul Rahim Asif; Muhammad Ishaq (Carbonates and Evaporites, 2025)

Development of a robust enzyme cascade system: co-immobilization of laccase and versatile peroxidase on polyacrylamide hydrogel for enhanced BPA degradation - Shagufta Kamal; Taleeha Roheen; Kanwal Rehman; Ismat Bibi; Muhammad Sajid Hamid Akash (Biodegradation, 2025)

Revealing Effects of Calcium-Based Formulations Focusing on Membrane Instability, Fruit Quality, Phytochemical Properties, and Disease Incidence in Peach (Prunus Persica) During Storage - Syed Tanveer Shah; Muhammad Sajid; Abdul Basit; Bibi Haleema; Ayesha Khan; Heba I. Mohamed (Applied Fruit Science, 2025)

Harvest Time Influences Quality and Storability of ‘Chandler’ Strawberries Grown Under Subtropical Conditions of Pakistan - Ayesha Maryam; Raheel Anwar; Mahmood Ul Hasan; Sajid Ali; Ahmad Sattar Khan; Muhammad Moaaz Ali; Khurram Ziaf (Applied Fruit Science, 2025)

Structural Load Optimization of 15 MW Offshore Wind Turbine Using LHS-Based Design Space - Sajid Ali; Muhammad Waleed; Daeyong Lee (Journal of Marine Science and Engineering, 2025)
The structural integrity of next-generation offshore wind turbines is highly sensitive to inflow variability, yet current standards often simplify wind conditions without capturing their combined effects on dynamic loads. To address this, we analyzed the NREL IEA 15 MW offshore wind turbine using 27 simulation cases strategically selected through Latin Hypercube Sampling (LHS) from a design space of over 14 million combinations. Four key environmental variables—Extreme Wind Speed (30–40 m/s), turbulence intensity (12–16%), Shear Exponent (0.1–0.3), and Flow Inclination Angle (−8° to +8°)—were varied to assess their influence on structural response using BLADED simulations. Results showed that the combined structural moment (Mxyz) ranged from 159,502.5 kNm (minimum) to 189,829.2 kNm (maximum), indicating a 19% increase due to inflow conditions. Maximum-moment case exhibited a 2.6× higher drag coefficient, a 13% rise in pitch bearing moment, and dominant frequency content near 0.175 Hz, closely matching the first tower side-side natural mode (0.17593 Hz), confirming potential resonance. These findings highlight the importance of multidimensional inflow modeling for identifying worst-case load scenarios and establishing a foundation for future load prediction models and support structure optimization.

Exploring Proteomic Alterations in Intellectual Disability: Insights from Hyperlipidemia and Hyperphosphatasia Subgroups - Soma Vankwani; Munazza Raza Mirza; Muhammad Tahir; Muhammad Wasim; Sajid Ali Rajput; Haq Nawaz Khan; Martin R. Larsen; Muhammad Iqbal Choudhary; Fazli Rabbi Awan (NeuroMolecular Medicine, 2025)

Academic stress and adolescent health: Exploring eating patterns, dietary preferences, and sleep duration in Pakistan's youth - Zahra Noor; Muniba Khaliq; Azmat Ullah Khan; Muhammad Asif Ali; Sajid Khan Tahir; Kashaf Khaliq (Appetite, 2025)

Rhizospheric crosstalk: A mechanistic overview of how plant secondary metabolites alleviate abiotic stresses - Ali Muhammad; Muhammad Hafeez Ullah Khan; Xiangjun Kong; Shuaichao Zheng; Na Bai; Lijie Li; Nina Zhang; Sajid Muhammad; Zengqiang Li; Xiaotian Zhang; Chen Miao; Zhiyong Zhang (Plant Science, 2025)

Carrageenan based edible coating modulates oxidative stress and delays cell wall polysaccharides disassembly in harvested grapefruit - Sajid Ali; Sidra Riaz; Hafiz Umer Javed; Ahmad Sattar Khan; Maratab Ali; Safina Naz; Hasan Sardar; Muhammad Shahzad Saleem (Journal of Stored Products Research, 2025)

A review on hydrogen production using decorated metal-organic frameworks by electrocatalytic and photocatalytic water splitting - Rana Adeel Mehmood; Awais Ali Aslam; Muhammad Javid Iqbal; Ali Hamza Sajid; Ameer Hamza; Hina Fatima Tahira; Izaz Ul Islam; Erdal Yabalak (Fuel, 2025)

Morpho-physiological attributes, antioxidant activities, proximate seed analysis, and phytoremediative prospective of two castor bean genotypes in lead spiked soil - Sahar Naveed; Sajid Mahmood; Wajid Ishaque; Muhammad Akhtar (Acta Physiologiae Plantarum, 2025)

Insight into polyethylene glycol-mediated physiochemical, nutritional, and antioxidative defense modulations in salt-stressed Raphanus sativus L - Muhammad Sajid; Shakil Ahmed; Rehana Sardar; Nasim Ahmad Yasin (Physiology and Molecular Biology of Plants, 2025)

Biochemical investigation of FOXP3 genetic polymorphism and its association with biochemical parameters in pre-eclampsia patients - Muhammad Sajid Hamid Akash; Francis Victor; Kanwal Rehman; Amjad Hussain; Mudassar Shahid; Asif Shahzad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Assessment of Climate-resilient Cotton Genotypes Exhibiting High-temperature Tolerance - Sajid Ali; Waqas Shafqat Chattha; Aziz Ullah; Muhammad Zahid Ihsan; Waqar Shafqat; Abdel-Halim Ghazy; Muhammad Afzal; Bilal Ayub (Journal of Crop Health, 2025)

Biological Approaches to Sustainable Management of Fusarium Wilt in Cotton - Iqra Javed; Muhammad Arslan Khan; Hasan Riaz; Shafqat Saeed; Muhammad Sajid; Muhammad Bashair; Zulqarnain Abbas; Haider Ali; Munirah Abdullah Al-Dosary; Muhammad Bilawal Junaid (Journal of Crop Health, 2025)

Dynamic Structural Behavior of Monopile Support Structure for 15 MW Offshore Wind Turbine During Different Phases of Operation - Sajid Ali; Muhammad Waleed; Daeyong Lee (Journal of Marine Science and Engineering, 2025)
The structural integrity of offshore wind turbine monopiles is critical for ensuring operational stability and long-term performance under varying environmental and aerodynamic loads. However, transient load conditions during different operational phases, such as start, normal stop, and emergency stop, can significantly impact structural behavior, influencing fatigue life and dynamic stability. This study investigates the dynamic structural response of a 15 MW offshore wind turbine monopile, incorporating modal analysis and transient simulations to assess deflection, forces, moments, and rotational displacements at the mud-line. The modal analysis revealed natural frequencies of 0.509492 Hz, 1.51616 Hz, and 3.078425 Hz for the blade’s flap-wise modes, while side-to-side modes for the combined tower and monopile structure were identified at 0.17593 Hz, 0.922308 Hz, and 1.650862 Hz. These frequencies are crucial in evaluating resonance risks and ensuring dynamic stability under combined aerodynamic and hydrodynamic forces. The transient analysis demonstrated that lateral force (Fy) variations peaked at −2500 kN during emergency stop, while moment fluctuations (My) reached ±100,000 kNm, reflecting the monopile’s high dynamic sensitivity under sudden aerodynamic unloading. Rotational displacements also showed significant variations, with θx oscillating up to ±0.0009 degrees and θy between −0.0022 and −0.0027 degrees. These findings provide valuable insights into optimizing monopile design to mitigate resonance effects, improve fatigue performance, and enhance structural resilience for large-scale offshore wind turbine support systems.

Potential role of inoculum size in biomass accumulation and antioxidant secondary metabolites production in adventitious root cultures of Stevia rebaudiana - Naveed Ahmad; Nisar Ahmad; Muhammad Sajid; Kamran Rauf; Mudassar Iqbal; Muhammad Numan; Irfan Ullah; Amir Khan; Wahidah H. Al-Qahtani; Mostafa A. Abdel-Maksoud; Hamada AbdElgawad; Babar Iqbal; et al. (Plant Biosystems, 2025)

Tracking the trace element pollution and associated health risk in urban coastal groundwater, eastern Saudi Arabia - Mohammed Benaafi; Bassam Tawabini; Shehzada Muhammad Sajid Jillani; Ali Mohammed Babalghaith; Isam H. Aljundi (Ocean & Coastal Management, 2025)

Increasing Salinity and Cadmium Enhanced Leaf Membrane Damage and H2O2 Production Irrespective of Reduced Sodium and Cadmium Accumulation in Wheat (Triticum aestivum L.) - Sajid Masood; Muhammad Ashraf; Mubshar Hussain; M. Farooq Azhar; M. Zafar-ul-Hye; Omer Farooq; Muhammad Aon; M. Tariq Javed (Journal of Soil Science and Plant Nutrition, 2025)

Citrus phytochemicals as potential therapeutics against asiatic citrus psyllid and Candidatus Liberibacter asiaticus: targeting the tripartite interaction - Muhammad Awais; Muhammad Ali; Mohsin Javed; Faisal Hanif; Muhammad Nouman; Ammar Zidan; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Abd-ElAziem Farouk; Ibrahim Jafri (Journal of Plant Pathology, 2025)

Novel mutations in exon 2 of follistatin (FST) gene associated with wool fiber diameter in sheep - Tahira Mir; Muhammad Ibrahim; Muhammad Siraj; Sajid Ali Khan Bangash; Sher Hayat Khan; Majid Khan; Muhammad Tayyab; Sohail Ahmad (Small Ruminant Research, 2025)

Biomitigation of noxious metal ions using engineered lignin-based nanocomposites for sustainable environment - Zaeem Bin Babar; Rashid Iftikhar; Komal Rizwan; Shahid Munir; Mashhood Urfi; Fawad Ashraf; Muhammad Ali Inam; Shahid Iqbal; Muhammad Saad; Sajid Mahmood; Nasser S. Awwad; Hala A. Ibrahium (Journal of Water Process Engineering, 2025)

Edge computing and transfer learning-based short-term load forecasting for residential and commercial buildings - Muhammad Sajid Iqbal; Muhammad Adnan (Energy and Buildings, 2025)

Physio-biochemical and molecular mechanisms of low nitrogen stress tolerance in peanut (Arachis hypogaea L.) - Xiangjun Kong; Rui Wang; Peipei Jia; Hengbin Li; Aziz Khan; Ali Muhammad; Sajid Fiaz; Qunce Xing; Zhiyong Zhang (Plant Molecular Biology, 2025)

Chemistry, biosynthesis, and theranostics of antioxidant flavonoids and polyphenolics of genus Rhododendron: an overview - Amjad Hussain; Sajjad Azam; Rabia Maqsood; Riaz Anwar; Muhammad Sajid Hamid Akash; Hidayat Hussain; Daijie Wang; Muhammad Imran; Katarzyna Kotwica-Mojzych; Shoaib Khan; Shabbir Hussain; Muhammad Adnan Ayub (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Correction: Discontinuity characterization for slope stability assessment using combined aerial photogrammetry, and geophysics approach - Muhammad Junaid; Rini Asnida Abdullah; Arshad Ullah; Radzuan Sa’ari; Sajid Mahmood; Hafeezur Rehman; Safi ur Rehman; Mahmut Sari (Natural Hazards, 2025)

Discontinuity characterization for slope stability assessment using combined aerial photogrammetry, and geophysics approach - Muhammad Junaid; Rini Asnida Abdullah; Arshad Ullah; Radzuan Sa’ari; Sajid Mahmood; Hafeezur Rehman; Safi ur Rehman; Mahmut Sari (Natural Hazards, 2025)

Disease resistance to tomato yellow leaf curl virus (TYLCV) enhanced by natural plant growth regulators and biopesticide - Sajid Mehmood; Marina Sajid; Tamsal Murtaza; Tanveer Hussain; Rana Naveed Ur Rehman; Muhammad Tahir Akram; Huma Abbas; Khadija Rafiq; Muhammad Kamran; Manzoor Hussain; Muhammad Inam ul Haq; Gull-e-laala Khan (Journal of Plant Diseases and Protection, 2025)

Phenotypic and Molecular Screening for Yellow Rust Resistance in Chinese Wheat Hybrids as Impacted by Selection - Zainab Iftikhar; Muhammad Arif; Aamir Iqbal; Iqbal Munir; Sheng Quan Zhang; Chang Ping Zhao; Sajid Ali (Journal of Crop Health, 2025)
Exploring the potential of novel sources of wheat material is immensely important to combat the ever-changing pathogen causing wheat rust disease, associated with huge losses worldwide. This study focused on assessing rust (YR) resistance in Chinese wheat hybrids, combining molecular markers and field testing over two years with estimation of the impact of selection. Out of 416 hybrids, 108 were selected based on disease scoring parameters, showing negative genetic advancement for rust severity and coefficient of infection. The maximum rust severity reached 100% for four hybrids during the year 2017–18 whereas 70% for three hybrids during the year 2018–19. The maximum coefficient of infection was observed for four hybrids which were 100% (2017–18), whereas 70% for three hybrids (2018–19). Molecular genotyping with a set of five yellow rust resistance genes linked markers revealed that the most frequent molecular markers was Yr18 / Lr34 (among the YR markers), present in 92 out of 108 hybrids. All the five Yr genes were present only in 18 hybrids. Yr18 was the most common resistance gene detected in 85% hybrids, while Yr17 was the least detected gene (57%). Notably, the average coefficient of infection (ACI) was not directly associated with the number of resistant genes. Considering the overall performance, the hybrid lines 17BH002, 17BH057, 17BH073, 17BH109, 17BH123, 17BH128, 17BH190, 18BH026 and 17BH155 had an overall low yellow rust severity and co-efficient of infection and could be considering promising lines for further utilization. Clustering based on rust resistance genes categorized hybrids into five main clusters for YR resistance genes, showing variability among these valuable genetic resources. The observed variability in this study can be utilized for future breeding programs focused on developing resistant wheat varieties.

Exploring environmentally stable and novel genetic factors influencing rice grain shape and yield attributes - Sadia Gull; Zulqarnain Haider; Houwen Gu; Saleem Uddin; Muhammad Qasim; Rana Ahsan Raza Khan; Adil Altaf; Sajid Fiaz; Mona S. Alwahibi; Mohamed S. Elshikh; Rashid Iqbal; Jun Miao; et al. (Euphytica, 2025)

Investigation of depositional fabric and its impact on the geomechanical behavior of limestones - Subhan Ullah; Muhammad Sajid; Khalid Latif; Abdul Rahim Asif; Muhammad Rizwan; Umair Mussawar; Shuja Ullah (Carbonates and Evaporites, 2025)

Exploring hotspots of traffic accidents in Chiniot-Sargodha Road, Punjab, Pakistan - Taimoor Ashraf; Muhammad Irfan Ahamad; Shakeel Mahmood; Jiangtao Fu; Muhammad Sajid Mehmood; Adnanul Rehman; Sohail Abbas; Syed Ali Asad Naqvi; Rana Muhammad Zulqarnain (Environment, Development and Sustainability, 2025)

Development and In-Vitro Tuning of Piperine Containing Solid Lipid Microparticles for the Treatment of Rheumatoid Arthritis - Muneeba Aziz; Sajid Bashir; Rai Muhammad Sarfraz; Hira Ijaz; Asif Mahmood; Zulcaif; Bilal Haroon; Milad A. Mezher; Mohamed M. Salem; Sami Al Zahrani; Mounir M. Bekhit (AAPS PharmSciTech, 2025)

Alleviation of cadmium stress and improved growth performance of periwinkle (Catharanthus roseus L.) by foliar application of zinc oxide nanoparticles - Muhammad Ahsan; Emanuele Radicetti; Roberto Mancinelli; Hayssam M. Ali; Adnan Younis; Mateen Sajid; Abdul Manan; Sajjad Ali; Mohammad Valipour; Hira Zulfiqar (South African Journal of Botany, 2025)

Titanium dioxide nanoparticles seed priming as a remedy for nickel-induced stress in maize through antioxidant enhancement and ultrastructural optimization - Muhammad Rehman; Abdul Salam; Bahar Ali; Irshan Ahmad; Muhammad Haseeb Javaid; Zulqarnain Haider; Raheel Munir; Muhammad Umair Yasin; Imran Ali; Chunyan Yang; Sajid Muhammad; Yinbo Gan (Journal of Environmental Management, 2025)

Tectono-magmatic evolution of the Indian crust in western Himalayas during Paleoproterozoic: Insights from Nanga Parbat and Indus syntaxis in northern Pakistan - Muhammad Sajid; Michael Wiedenbeck; Muhammad Arif; Johannes Glodny; Nowrad Ali; Humaad Ghani; Jessica A. Stammeier (Gondwana Research, 2025)

Nanosilica and salicylic acid synergistically regulate cadmium toxicity in rice - Sajid Muhammad; Zaid Ulhassan; Raheel Munir; Muhammad Umair Yasin; Faisal Islam; Kangni Zhang; Weiqi Chen; Mehmood Jan; Muhammad Afzal; Ali Muhammad; Fakhir Hannan; Weijun Zhou (Environmental Pollution, 2025)

Identifying multidrug-resistant organisms in diabetic foot ulcers: a study of risk factors and antimicrobial resistance genes - Mohd Saleem; Soha Abdallah Moursi; Tahani Nasser Almofeed Altamimi; Alharbi Mohammed Salem; Alwaleed Mohammad Alaskar; Sahar Adly Hassan Hammam; Ehab Rakha; Syed Muhammad Ozair Ilyas; Hamoud Abdulmohsin Al-Malaq; Metab Nasser Alshammari; Azharuddin Sajid Syed Khaja (World Journal of Microbiology and Biotechnology, 2025)

Exploration of molecular interactions responsible for anti-inflammatory attributes of GI friendly micro-sized formulation of flurbiprofen and clove oil - Hafiz Muhammad Zubair; Mohamed Farouk Elsadek; Sajid Asghar; Khalid S. Al-Numair; Malik Saadullah; Shafqat Rasul Chaudhry; Thomas Efferth; Muhammad Asif (Inflammopharmacology, 2025)

Transcriptome-wide identification of microRNAs regulating plant immunity in Gossypium arboreum L. - Abdul Manan Khan; Muhammad Abu Bakar Saddique; Sajid Fiaz; Saba Zafar; Kotb A. Attia; Yaser M. Hafez; Arif Ahmed Mohammed (Genetic Resources and Crop Evolution, 2025)

An integrated approach for GLOF hazard, vulnerability and risk assessment in the Karakoram Mountain Range of northern Pakistan - Sajid Ullah; Muhammad Shafique; Ghazanfar Ali Khattak; Attaullah Shah; Yaseen Ullah (Journal of Mountain Science, 2025)

Revolutionizing Fingerprint Detection: Ce3+ Doped SiO2-Zr2O3:Sr2+ Nanocomposites with Enhanced Luminescence and Selectivity - Momna Qayyum; Sammia Shahid; Sana Mansoor; Muhammad Faizan; Mohsin Javed; Ammar Zidan; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Abd-ElAziem Farouk; Salman Aloufi (Journal of Fluorescence, 2024)
Even though fingerprints remain one of the most reliable methods of identification, they are often lost during the recovery process. Accurate fingerprint recognition depends on the contrast between the ridges and substrate. On tough surfaces, such as glossy, colorful, and patterned materials, the contrast is harder to establish. Photoluminescent materials play a crucial role in forensic investigations as they enable the development of procedures that enhance image quality and increase the accuracy of findings from security institutions. Due to the strong emission in the red area at 620 nm, the use of trivalent Rare Earth ions (RE 3+ ) doped materials in this work is notable. Because of the unique properties and abundance of cerium, luminous materials based on SiO 2 -Zr 2 O 3 : Ce 3+ , Sr 2+ prepared via sol-gel technique present a more practical alternative for use in criminal investigations compared to current photonic materials. The sample was further co-doped with synthetic (Safranin-O and crystal violet) as well as organic (curcumin and lycopene) photoluminescent dyes. The nanocomposites were examined using X-ray diffraction analysis (XRD), energy-dispersive X-ray analysis (EDX), dynamic light scattering (DLS), scanning electron microscopy (SEM), and photoluminescence spectroscopy (PL). In conclusion, this work highlights the qualities critical to obtaining higher-resolution latent fingerprint images for potential forensic applications.

Suppression of canary grass (Phalaris minor) with simultaneous use of rhizobacteria and sunflower allelopathy - Abubakar Dar; Umme Habiba; Muhammad Tauseef Jaffar; Maqshoof Ahmad; Azhar Hussain; Umar Farooq; Sajid Mehmood Nadeem; Muhammad Zahid Mumtaz; Usman Zulfiqar; Abd El-Zaher M.A. Mustafa; Mohamed S. Elshikh (Rhizosphere, 2024)

Spatial distribution, ecological and human health risks of potentially toxic elements (PTEs) in river Ravi, Pakistan: A comprehensive study - Muhammad Irfan Ahamad; Adnanul Rehman; Muhammad Sajid Mehmood; Shakeel Mahmood; Zeeshan Zafar; Heli Lu; Wanfu Feng; Siqi Lu (Environmental Research, 2024)

Sirtuin insights: bridging the gap between cellular processes and therapeutic applications - Shagufta Kamal; Sharon Babar; Waqas Ali; Kanwal Rehman; Amjad Hussain; Muhammad Sajid Hamid Akash (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Molecular genetics, neuroimaging outcomes, and structural analyses of novel and recurrent variants of WDR62 gene in two consanguineous Pakistani families with autosomal recessive primary microcephaly - Komal Aslam; Aysha Saeed; Hafiza Iqra Saeed; Rasheeda Bashir; Hanna Abid; Roeha Akhtar; Nida Habib; Ramisha Khan; Roha Asif; Shereen Rafiq; Maria Asif; Ehtisham Ul Haq Makhdoom; et al. (Molecular Biology Reports, 2024)

An SNP based genotyping assay for genes associated with drought tolerance in bread wheat - Abdul Rauf; Muhammad Ali Sher; Umar Farooq; Awais Rasheed; Muhammad Sajjad; Ruilian Jing; Zulqurnain Khan; KOTB A. Attia; Arif Ahmed Mohammed; Sajid Fiaz; Jing Chen; Shoaib Ur Rehman (Molecular Biology Reports, 2024)

Investigating the effects of a single ASPM variant (c.8508_8509) on brain architecture among siblings in a consanguineous Pakistani family - Komal Aslam; Aysha Saeed; Iffat Jamil; Hafiza Iqra Saeed; Ramisha Khan; Samina Hassan; Shereen Rafiq; Maria Asif; Ehtisham Ul Haq Makhdoom; Rasheeda Bashir; Muhammad Sajid Hussain; Shahid Mahmood Baig; et al. (Molecular Biology Reports, 2024)

The comparative transcriptome analysis of two green super rice genotypes with varying tolerance to salt stress - Nageen Zahra; Muhammad Uzair; Imdad Ullah Zaid; Kotb A. Attia; Safeena Inam; Sajid Fiaz; Rizk M. Abdallah; Muhammad Kashif Naeem; Umer Farooq; Nazia Rehman; Ghulam Muhammad Ali; Jianlong Xu; et al. (Molecular Biology Reports, 2024)

MicroRNA expression profiling of ovine epithelial cells stimulated with the Staphylococcus aureus in vitro - Ghulam Asghar Sajid; Muhammad Jasim Uddin; Saif Adil Abbood Al-Janabi; Abdiaziz Nur Ibrahim; Mehmet Ulas Cinar (Mammalian Genome, 2024)

Cationic polymer-mediated interbacterial aggregation: A novel approach for rapid aerobic granules development - Sajid Hussain; Khan Muhammad Brohi; Umberto Gallina; Gianni Andreottola (Chemosphere, 2024)

Exploring fruit ripening methods: Conventional, artificial, and novel approaches for quality and health - Usama Nasir; Amir Ismail; Muhammad Riaz; Kashif Razzaq; Sajid Ali; Ajaz Hussain; Mavra Ameen; Asifa Saif; Farwa Aslam; Carlos Augusto Fernandes de Oliveira (Food Control, 2024)

Does conflict aggravate energy poverty? - Usman Khalid; Muhammad Shafiullah; Sajid M. Chaudhry (Energy Policy, 2024)

Proximate composition and prevalence and exposure assessment of aflatoxins intake through consumption of fresh carrot and processed marketed carrot products in South Punjab, Pakistan - Aneela Nijabat; Shahwana Bibi; Maryam Ajmal; Saher Nawaz; Muhammad Zaheer Sajid; Saad Ullah Khan Leghari; Muhammad Mahmood-ur-Rehman; Naima Huma Naveed; Aamir Ali; Philipp W. Simon (Natural Product Research, 2024)

Risk and retraction: asymmetric nexus between monetary policy uncertainty and eco-friendly investment - Lansheng Cao; Ding Jin; Sajid Ali; Muhammad Saeed Meo; Raima Nazar (Stochastic Environmental Research and Risk Assessment, 2024)

In silico genome-wide analysis of the growth-regulating factor gene family and their expression profiling in Vitis vinifera under biotic stress - Nimra Nazir; Azhar Iqbal; Hadia Hussain; Faisal Ali; Khalid S. Almaary; Most. Nazmin Aktar; Muhammad Sajid; Mohammed Bourhia; Ahmad Mohammad Salamatullah (Cell Biochemistry and Biophysics, 2024)

Emerging paradigms in two-dimensional materials: Classification, synthesis, and the role of defects in electrocatalysis for water splitting and oxygen reduction reaction - Muhammad Sajid; Muhammad Azam Qamar; Ahmad Farhan; Wajeeha Qayyum; Aman Khalid; Aqsa Nawaz; Shern-long Lee; Haq Nawaz (Journal of Environmental Chemical Engineering, 2024)

An electrochemical sensing potential of cobalt oxide nanoparticles towards citric acid integrated with computational approach in food and biological media - Huma Ajab; Ali Turab Jafry; Hasnain Sajid; Matthew A. Addicoat; Khurshid Ayub; Muhammad Zia Ul Haq (Food Chemistry, 2024)

Identification, charectrization and genetic transformation of lignin and pectin polysaccharides through CRISPR/Cas9 in Nicotiana tobacum - Rana Imtiaz Ahmed; Angyan Ren; Dalal Sulaiman Alshaya; Sajid Fiaz; Yingzhen Kong; Shoaib Liaqat; Naushad Ali; Muhammad Abu Bakar Saddique; Kotb A. Attia; Mahmood Ul Hassan Taga (Functional & Integrative Genomics, 2024)

Prediction of RNA editing sites in maize under salt stress through transcriptomic approaches - Dalal Sulaiman Alshaya; Muhammad Uzair; Obaid Ur Rehman; Kotb A. Attia; M. H. Mubarak; Sajid Fiaz (Plant Biotechnology Reports, 2024)

Evaluation of Heavy Metal Concentration in Different Organs of Labeo rohita in Water and Sediment of Marala Ravi Link Canal (MRL) and Upper Chenab Canal (UCC) of Chenab River, Pakistan, and Their Health Implications - Waqas Ahmad; Muhammad Samee Mubarik; Sajid Yaqub Qureshi; Naveed Ahmad Khan (Biological Trace Element Research, 2024)

Microplastic pollution in aquatic ecosystem: A review of existing policies and regulations - Muhammad Tariq Khan; Sajid Rashid; Unzile Yaman; Saeed Ahsan Khalid; Asif Kamal; Mushtaq Ahmad; Nasrin Akther; Md Abul Kashem; Md Faysal Hossain; Wajid Rashid (Chemosphere, 2024)

Prediction of Nili-Ravi buffalo bull fertility through Fourier harmonic analysis of sperm - Javeria Arshad; John J. Parrish; Muhammad Amjad Awan; Bushra Allah Rakha; Muhammad Waseem; Muhammad Sheeraz Ahmad; Sajid Iqbal; Shamim Akhter (Theriogenology, 2024)

Dynamic interplay of silica-coated iron oxide nanocomposite on soil-plant system to mitigate Cd toxicity in rice - Faisal Islam; Muhammad Saad Shoaib Khan; Sulaiman Ahmed; Aziz Ul Ikram; Fakhir Hannan; Mehmood Jan; Muhammad Sajid; Ali Ahmed Zaky Shoaib; Shan Liu; Jian Chen (Journal of Cleaner Production, 2024)

Engineering of interfacial electric field by g-C3N4/ZnSnO3 heterojunction for excellent photocatalytic applications - Zia Ur Rehman; Sajid Ur Rehman; Muhammad Bilal; Faheem K. Butt; Asif Hussain; Jawad Ahmad Jrar; Kewang Zheng; Yongcai Zhang; Xiaoyong Xu; Xiaozhi Wang; Jianhua Hou (Journal of Cleaner Production, 2024)

Biosafety measures for Alicyclobacillus spp. strains across various levels of biohazard - Marina Sajid; Sajid Mehmood; Yahong Yuan; Tianli Yue; Muhammad Zubair Khalid; Ahmad Mujtaba; Sulaiman Ali Alharbi; Mohammad Javed Ansari; Abdellah Zinedine; João Miguel Rocha (Food and Chemical Toxicology, 2024)

Molecular Characterization and Comparative Transcriptomic Analysis of Hr-Lcyb and Hr-Psy Genes for Carotenoids Synthesis in Sea Buckthorn (Hippophae rhamnoides L.) - Shazia Arif; Hafiz Muhammad Ahmed; Safira Attacha; Kotb A. Attia; Arif Ahmed Mohammed; Saira Ishaq; Shahid Iqbal Awan; Sajid Fiaz; Waseem Alam; Seung Hwan Yang (Journal of Soil Science and Plant Nutrition, 2024)

Alleviating Drought Stress in Strawberry Plants: Unraveling the Role of Paclobutrazol as a Growth Regulator and Reducer of Oxidative Stress Induced by Reactive Oxygen and Carbonyl Species - Khansa Saleem; Muhammad Ahsan Asghar; Ali Raza; Kaiwen Pan; Abd Ullah; Hafiz Hassan Javed; Mahmoud F. Seleiman; Shakeel Imran; Sajid Mehmood Nadeem; Khurram Shehzad Khan; Junbo Du; Fei Xu; et al. (Journal of Plant Growth Regulation, 2024)

Skipping irrigation at pre- and post-anthesis stages influences grain yield and starch contents of bread wheat derived from synthetic or landraces - Sajid Shokat; Mian Abdur Rehman Arif; Muhammad Qandeel Waheed; Fulai Liu; Carlos Guzmán; Sukhwinder Singh (Cereal Research Communications, 2024)
This study aims to evaluate the role of genetic diversity originated from three-way crosses of landraces and synthetic bread wheat derivatives attempted with elite cultivars to identify the genotypes having better grain yield as well as better starch contents under flowering stage drought stress. In total, 50 genotypes comprised of 47 derivatives of landraces and synthetics, and three standard varieties were grown in the fields of CIMMYT, Obregon following alpha lattice design with two replications. Drought stress was imposed by stopping the irrigation before anthesis and post-anthesis stages. Different traits related to physiological adaptations, earliness, grain yield and starch contents were decreased under drought stress except amylose which increased significantly. Canopy temperature depression was not significantly affected by drought stress. Further, we identified strong correlation of grain yield with plant height, normalized difference in vegetation index, plant maturity, spike length, grain number and thousand grain weight but negative with canopy temperature depression. Non-significant correlation of amylose and amylopectin was recorded with grain yield. Results revealed that genetic diversity derived from landraces and synthetic bread wheat can improve grain yield and starch contents but simultaneous improvement of both is elusive.

Non-linear ground deformation detection and monitoring using time series InSAR along the coastal urban areas of Pakistan - Sajid Hussain; Bin Pan; Zeeshan Afzal; Wajid Hussain; Yin Jianhui; Meer Muhammad Sajjad; Muhammad Ali (Environmental Science and Pollution Research, 2024)

Microplastics in agroecosystems: Soil-plant dynamics and effective remediation approaches - Muhammad Tayyab; Syed Shabi Ul Hassan Kazmi; Paolo Pastorino; Hafiz Sohaib Ahmed Saqib; Zaher Mundher Yaseen; Muhammad Sajid Hanif; Waqar Islam (Chemosphere, 2024)

Purifying surface water contaminated with azo dyes using nanofiltration: Interactions between dyes and dissolved organic matter - Mian Jawaduddin; Zhaoyang Su; Muhammad Saboor Siddique; Sajid Rashid; Wenzheng Yu (Chemosphere, 2024)

In-tube solid phase extraction with graphitic-based polyurethane sponge as a superhydrophobic sorbent and determination of drug residues in foodstuffs using high-performance liquid chromatography - Sidra Iram; Zahra Nazar; Muhammad Sajid; Thomas William Chamberlain; Muhammad Furqan Nawaz; Muhammad Mahboob Ahmed; Muhammad Kashif (Food Chemistry, 2024)

Deep eutectic solvents as sustainable extraction media for extraction of polysaccharides from natural sources: Status, challenges and prospects - Noorfatimah Yahaya; Ahmad Husaini Mohamed; Muhammad Sajid; Nur Nadhirah Mohamad Zain; Pao-Chi Liao; Kit Wayne Chew (Carbohydrate Polymers, 2024)

Phenotypic and Molecular Profiling of Vitis Vinifera L. Genotypes Against Anthracnose Through SCAR Markers - Qandeela Nigar; Mahmood ul Hassan; Rashid Mehmood Rana; Sadia Mehmood Satti; Summaira Ali; Muhammad Farhan Khan Pasha; Irfan Ali; Hafiz Muhamamd Ahmad; Sami Al Obaid; Mohammad Javed Ansari; Sajid Fiaz (Journal of Crop Health, 2024)

Plant growth promoting Dictyosphaerium DHM2 derived magnesium peroxide nanoparticles with antibacterial, antioxidant and photocatalytic properties - Kausar Chaudhary; Shafia Maryam; Sajid Iqbal; Abdullah Ahmad; Muhammad Tahir; Hussnain Ahmed Janjua (Algal Research, 2024)

Surviving chlorinated waters: bleaching sensitivity and persistence of free-living amoebae - Muhammad Tariq Zahid; Ghulam Mustafa; Romasa Sajid; Ayesha Razzaq; Muzdalfa Waheed; Moonis Ali Khan; Jae-Hoon Hwang; Young Kwon Park; Woo Jin Chung; Byong-hun Jeon (Environmental Science and Pollution Research, 2024)

In vitro exploration of Acinetobacter strain (SG-5) for antioxidative potential and phytohormone biosynthesis in maize (Zea mays L.) cultivars differing in cadmium tolerance - Saghir Abbas; Kashif Tanwir; Muhammad Hussaan; Sajid Masood; Qasim Ali; Ali Raza; Muhammad Shahid; Hassan Javed Chaudhary; Saba Mushtaq; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2024)

Enhancing drought tolerance in broccoli (Brassica oleracea L.) through melatonin application: Physiological and biochemical insights into growth, photosynthesis, and antioxidant defense mechanisms - Hasan Sardar; Muhammad Shafiq; Safina Naz; Sajid Ali; Riaz Ahmad; Shaghef Ejaz (Biocatalysis and Agricultural Biotechnology, 2024)

Silicon and Biochar Synergistically Stimulate Nutrients Uptake, Photosynthetic Pigments, Gaseous Exchange and Oxidative Defense to Improve Maize Growth Under Salinity - Sajid Mahmood; Samir G. Al-Solaimani; Samrah Shams; Sahar Naveed; Basit Haider; Muhammad Naveed; Rehmat Ali; Muhammad Waqas (Water, Air, & Soil Pollution, 2024)

Sustainability in shaky times: analysing the resilience of green bonds amid economic policy uncertainty - Xichen Liu; Sajid Ali; Raima Nazar; Muhammad Saeed Meo (Stochastic Environmental Research and Risk Assessment, 2024)

Maize productivity and nutrient status in response to crop residue mineralization with beneficial microbes under various tillage practices - Haris Khan; Ahmad Khan; Sajid Khan; Anjum Anjum; Habib Akbar; Dost Muhammad (Soil and Tillage Research, 2024)

Florfenicol removal from veterinary pharmaceutical effluents: Tri-metallic zeolite 5A° for electrochemical oxidation and catalytic ceramic membrane separation - Amir Ikhlaq; Maryam Gull; Afnan Sajid; Khurram Saleem Joya; Muhammad Raashid; Osama Shaheen Rizvi; Zafar Masood; Salman Ahmed; Maryam Abid; Maham Hanif; Hafiz Abdul Aziz; Thamer Abdulhameed Al Johani; et al. (Journal of Environmental Chemical Engineering, 2024)

Yeast-based solutions in controlling plant pathogens - Amjad Ali; Fatih Ölmez; Muhammad Ahmad Zeshan; Mustansar Mubeen; Yasir Iftikhar; Ashara Sajid; Muhammad Abid; Ajay Kumar; Praveen Kumar Divvela; Manoj Kumar Solanki (Biocatalysis and Agricultural Biotechnology, 2024)

Characterization of the tubby-like proteins (TLPs) gene family in Cucumis sativus L.: insights into the evolution, structure, and expression patterns under salt stress - Ikram Ullah; Muhammad Uzair; Obaid Ur Rehman; Safira Attacha; Kotb A. Attia; Sheraz Ahmad; Muhammad Salman; Hamid Ali; Muhammad Abdul Rehman Rashid; Asmaa M. Abushady; Sajid Fiaz; Syed Jehangir Shah; et al. (Genetic Resources and Crop Evolution, 2024)

Heavy metal exposure and metabolomics analysis: an emerging frontier in environmental health - Kainat Ilyas; Hajra Iqbal; Muhammad Sajid Hamid Akash; Kanwal Rehman; Amjad Hussain (Environmental Science and Pollution Research, 2024)

Sustainable performance and disaster management in the oil and gas industry: An intellectual capital perspective - Sajid Nazir; Mahmood Ali; Munazza Saeed; Muhammad Shahzad Mubarik; Qasim Jalil (Resources Policy, 2024)

Impact of heavy metals on aquatic life and human health: a case study of River Ravi Pakistan - Muhammad Irfan Ahamad; Zijie Yao; Liang Ren; Cheng Zhang; Tingting Li; Heli Lu; Muhammad Sajid Mehmood; Adnanul Rehman; Muhammad Adil; Siqi Lu; Wanfu Feng (Frontiers in Marine Science, 2024)
Heavy-metal contamination in river and ocean is a critical environmental issue that endangers marine ecosystems and human health. Therefore, conducting extensive research to devise effective mitigation measures is imperative. Sediment samples were taken randomly throughout the study area. Analysis was done to determine the presence of different metals, including arsenic, cadmium, chromium, nickel, copper, zinc, lead, and manganese. The assessment of different pollution levels was done by using various pollution indicators including “geo-accumulation index (Igeo), contamination factor (CF), enrichment factor (EF)” for accuracy. The Igeo measurement for Cd indicated varying pollution, ranging from moderate to significantly polluted, while Mn revealed no contamination. Elements such as Ni, Cr, Cu, and Zn showed a moderate level of contamination. The contamination factor values exhibited a range of 0.436 (Pb) to 7.637 (Cd), with average values spanning from 0.9176 (Mn) to 4.9714 (Cd), suggesting significant regional variation. EF exhibits a pattern of contamination comparable to that of Igeo. The noncarcinogenic risk associated with exposure to Cd and As exceeded the higher limit (HI > 1) for children and adults. Furthermore, the carcinogenic risk presented by pollutants such as copper (Cu), arsenic (As), nickel (Ni), cadmium (Cd), and chromium (Cr) was found to exceed the limits in children. In adults, only arsenic (As) and copper (Cu) were shown to represent a higher risk of cancer than the limit of 10 −4 . The PCA analysis revealed that two (PCs) accounted for more than 65% of the total variance in the River Ravi, as determined by eigenvalues greater than 1. This study underscores the importance of the ongoing monitoring and management of heavy-metal pollution to ensure sustainable marine ecosystem development and public health protection.

Global Patterns of Agricultural Machine and Equipment Injuries- A Systematic Literature Review - Mian Muhammad Sajid Raza; Sihan Li; Salah F. Issa (Journal of Agromedicine, 2024)

Agricultural Injury Surveillance in the United States and Canada: A Systematic Literature Review - Sihan Li; Mian Muhammad Sajid Raza; Salah Issa (Journal of Agromedicine, 2024)

The synergetic impact of digital campaigns and economic incentives on environmental performance: the mediating role of household indoor and outdoor activities - Shahzad Ali; Muhammad Boota; Warda Sajid Khan; Mehrooz Khan; Mubashar Ali (Environmental Science and Pollution Research, 2024)

Study loss of vegetative cover and increased land surface temperature through remote sensing strategies under the inter-annual climate variability in Jinhua–Quzhou basin, China - Shahzad Ali; Abdul Basit; Sajid Ali; Muhammad Umair; Tyan Alice Makanda; Mohammed Rafi Shaik; Mujeeb Khan (Environmental Science and Pollution Research, 2024)

Sustainability assessment of biofuel and value-added product from organic fraction of municipal solid waste - Farayi Musharavati; Anees Ahmad; Muhammad Hassan Javed; Khadija Sajid; Muhammad Naqvi (Environmental Research, 2024)

Cambrian integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Zhixin Sun; Lang Sun; Fangchen Zhao; Bing Pan; Malik Muhammad Saud Sajid Khan; Shehryar Ahmed; Chuan Yang; Lanyun Miao; Zongjun Yin; Guoxiang Li; Maoyan Zhu (Science China Earth Sciences, 2024)

Cryogenian and Ediacaran integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Lang Sun; Malik Muhammad Saud Sajid Khan; Chuan Yang; Zhixin Sun; Bing Pan; Shehryar Ahmed; Lanyun Miao; Weichen Sun; Chunlin Hu; Xiaojuan Sun; Cui Luo; Bo Chen; et al. (Science China Earth Sciences, 2024)

Genetics aspect of vitamin C (Ascorbic Acid) biosynthesis and signaling pathways in fruits and vegetables crops - Adnan Sami; Shiming Han; Muhammad Zeshan Haider; Rameen Khizar; Qurban Ali; Muhammad Shafiq; Javaria Tabassum; Muhammad Nouman Khalid; Muhammad Arshad Javed; Mateen Sajid; Muhammad Aamir Manzoor; Irfan Ali Sabir (Functional & Integrative Genomics, 2024)

Remimazolam versus propofol for sedation in gastrointestinal endoscopy and colonoscopy within elderly patients: a meta-analysis of randomized controlled trials - Wania Ahmer; Sahar Imtiaz; Daniyal Muhammad Alam; Khadija Ahmed; Barka Sajid; Juvairia Yousuf; Sunny Asnani; Muhammad Ahmed Ali Fahim; Rahmeen Ali; Marium Mansoor; Muhammad Talha Safdar; Muhammad Umair Anjum; et al. (European Journal of Clinical Pharmacology, 2024)

Assessment of historical and projected changes in extreme temperatures of Balochistan, Pakistan using extreme value theory - Darakshan Naeem; Rizwan Aziz; Muhammad Awais; Sajid Rashid Ahmad (Environmental Monitoring and Assessment, 2024)

Predicting asphaltene adsorption on Fe3O4 nanoparticle using machine learning algorithms - Syed Imran Ali; Shaine Mohammadali Lalji; Usama Ahsan; Syed Muhammad Ali; Yassar Kamal Zia; Sajid Hussain; Muneeb Burney; Muhammad Qasim; Zeeshan Ahmad Arfeen (Arabian Journal of Geosciences, 2024)

Enhancing the Quality and Fruit Yield of Sweet Cherry (Prunus Avium) Cultivars by Foliar Application of Boron - Muhammad Sajid; Abdul Basit; Syed Tanveer Shah; Ayesha Khan; Izhar Ullah; Muhammad Bilal; Muhammad Suleman Khan; Waleed Khan (Applied Fruit Science, 2024)

Degradation of agricultural waste is dependent on chemical fertilizers in long-term paddy-dry rotation field - Farhan Nabi; Hong Chen; Sumbal Sajid; Guotao Yang; Yun Kyung; Syed Muhammad Mustajab Shah; Xuechun Wang; Yungao Hu (Journal of Environmental Management, 2024)

Empirical analysis of cost-effective and equitable solid waste management systems: Environmental and economic perspectives - Asif Iqbal; Abdullah Yasar; Abdul-Sattar Nizami; Rafia Haider; Imran Ali Sultan; Aman Anwer Kedwaii; Muhammad Murtaza Chaudhary; Muhammad Hassan Javed; Anees Ahmad; Khadija Sajid; Muhammad Naqvi; Muhammad Usman Ghori (Environmental Research, 2024)

Vegetable Plant Canopy Inhibits Soil Urease Activity and Reduces NH3 Losses Under p-Phenylenediamine (PPD)-Coated Urea Application - Sarah Shakeel; Rashid Mahmood; Ammara Fatima; Faisal Nadeem; Sajid Ali; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2024)

Interactive mode of biochar-based silicon and iron nanoparticles mitigated Cd-toxicity in maize - Muhammad Umair Yasin; Fakhir Hannan; Raheel Munir; Sajid Muhammad; Muhammad Iqbal; Iqra Yasin; Muhammad Saad Shoaib Khan; Farah Kanwal; Yang Chunyan; Xingming Fan; Yinbo Gan (Science of The Total Environment, 2024)

Risk surveillance with spatial distribution of Organochlorine Pesticides (OCPs) from sedimentary samples of Chenab River - Sidra Siddique; M. Nawaz Chaudhry; Sajid Rashid Ahmad; Rabia Nazir; Rimsha Javed; Muhammad Rashid Hafeez; Yasser Alraey; Lalita Ambigai Sivasamugham; Adeel Mahmood (Science of The Total Environment, 2024)

Recent trends in hydrogen-associated treatments for maintaining the postharvest quality of fresh and fresh-cut fruits and vegetables: A review - Maratab Ali; Sara Batool; Nauman Khalid; Sajid Ali; Muhammad Ammar Raza; Xiaoan Li; Fujun Li; Zhang Xinhua (Food Control, 2024)

Theoretical and experimental explored tailored hybrid H+/O2– ions conduction: Bridged for high performance fuel cell and water electrolysis - Zuhra Tayyab; Sajid Rauf; Muhammad Bilal Hanif; Hafiz Imran Ahmad Qazi; Naveed Mushtaq; Martin Motola; Sining Yun; Chen Xia; Dmitry A. Medvedev; Muhammad Imran Asghar; Abdullah N. Alodhayb; Arshad Hussain; et al. (Chemical Engineering Journal, 2024)

Genome-wide association study reveals novel genes on different chromosomal positions regulating boll weight in upland cotton (Gossypium hirsutum L.) - Zubair Iqbal; Muhammad Shahid Iqbal; Salman Alamery; Khurram Shehzad; Qamar U. Zaman; Safira Attacha; Zareen Sarfraz; Mian Faisal Nazir; Daowu Hu; Muhammad Mubashar Zafar; Aqib Zeb; Shoupuhe; et al. (Genetic Resources and Crop Evolution, 2024)

Melatonin alleviated cadmium accumulation and toxicity by modulating phytohormonal balance and antioxidant metabolism in rice - Raheel Munir; Muhammad Umair Yasin; Muhammad Afzal; Mehmood Jan; Sajid Muhammad; Nazia Jan; Chen Nana; Faisal Munir; Hamza Iqbal; Faiza Tawab; Yinbo Gan (Chemosphere, 2024)

Cerium oxide nanoparticles improve the post-thaw quality and in-vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Muhammad Shahbaz Yousaf; Nisar Ahmad; Sajid Khan Tahir; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman; Hafsa Zaneb; et al. (Theriogenology, 2024)

Magnetic solid phase extraction of aminoglycosides residue in chicken egg samples using Fe3O4-GO-Agarose-Chitosan composite - Muhammad Sajjad; Rasmiah Almufarij; Zeeshan Ali; Muhammad Sajid; Nadeem Raza; Suryyia Manzoor; Muhammad Hayat; Ehab A. Abdelrahman (Food Chemistry, 2024)

Correction: Molecular characterization of bread quality contributing high and low‑molecular‑weight glutenin subunits in Pakistani spring wheat genotypes - Muhammad Ammar Bashir; Muhammad Kashif; Imran Habib; Shahid Nazir; Amer Mumtaz; Sajid ur Rahman (Genetic Resources and Crop Evolution, 2024)

Molecular characterization of bread quality contributing high and low-molecular-weight glutenin subunits in Pakistani spring wheat genotypes - Muhammad Ammar Bashir; Muhammad Kashif; Imran Habib; Shahid Nazir; Amer Mumtaz; Sajid ur Rahman (Genetic Resources and Crop Evolution, 2024)

Evaluating the symmetric and asymmetric effectiveness of low carbon energy consumption for ecological footprint in China: the role of environment-related technological innovation - Xin Jin; Cheng Guo; Waheed Ahmad; Muhammad Sajid Ameen; Shujaat Abbas (Environmental Science and Pollution Research, 2023)

Comparative genomics of light harvesting chlorophyll (LHC) gene family and impact of chlorophyll-A contents under drought stress in Helianthus annuus - Parwsha Zaib; Hafiz Muhammad Ahmad; Safira Attacha; Mahmood-Ur Rahman; Muhammad Rizwan Shafiq; Kousar Parveen; Sajid Fiaz; Kotb A. Attia; Saira Ishaq; Shazia Arif; Asmaa M. Abushady; Muhammad Jawad Umer (Journal of Plant Physiology, 2023)

Spatio-temporal patterns of human-carnivore conflict and mitigation in Pakistan - Muhammad Danish; Tariq Mahmood; Faraz Akrim; Muhammad Sajid Nadeem; Shumaila Noreen; Nadeem Munawar; Muhammad Shakil; Muhammad Arshad (Journal for Nature Conservation, 2023)

ZnO nanoparticles mediated by Azadirachta indica as nano fertilizer: Improvement in physiological and biochemical indices of Zea mays grown in Cr-contaminated soil - Sajid Mehmood; Wenjie Ou; Waqas Ahmed; Jochen Bundschuh; Muhammad Rizwan; Mohsin Mahmood; Haider Sultan; Juha M. Alatalo; Ahmed S.M. Elnahal; Wenjie Liu; Weidong Li (Environmental Pollution, 2023)

Field response and molecular screening of European wheat germplasm against powdery mildew at the Himalayan region of Pakistan - Aamir Iqbal; Zia Ur Rehman; Muhammad Rameez Khan; Amir Muhammad Khan; Shahid Ullah Khan; Muhammad Arif; Javaid Iqbal; Mujeeb Ur Rehman; Minhaj Ali; Muhammad Qasim; Imran Ali; Zakir Hussain Facho; et al. (Journal of Applied Genetics, 2023)

Genome-wide identification and expression analysis of U-box gene family in Juglans regia L. - Hanif Khan; Umar Zeb; Sadaf Gul; Azizullah Aziziullah; Naushad Ali; Sajid Fiaz; Asmaa M. Abushady; Shariat Ullah; Salar Muhammad; Kotb A. Attia; Itoh Kimiko; Fengjie Cui; et al. (Genetic Resources and Crop Evolution, 2023)

Genetic characterization of coarse and basmati rice (Oryza sativa L.) through microsatellite markers and morpho-agronomic traits - Tahira Luqman; Zia-ul Qamar; Aqsa Tabasum; Wael. H. El-Kallawy; Talha Nazir; Safira Attacha; Sajid Fiaz; Muhammad Azhar Nadeem; Amjad Hameed; Zahra Maryum; Itoh Kimiko; Kotb Attia (Genetic Resources and Crop Evolution, 2023)

Correction: Modeling future urban network capacity and land use/land cover simulation using GEE and remote sensing data - Muhammad Nabeel Khalid; Muhammad Nasar Ahmad; Muhammad Asif Javed; Sajid Rashid Ahmad (Arabian Journal of Geosciences, 2023)

Genome-wide characterization and expression analysis of cyclic nucleotide-gated ion channels (CNGCs) gene family in Arabidopsis thaliana L. and Helianthus annuus L. for drought stress - Sadaf Oranab; Hafiz Muhammad Ahmad; Sajid Fiaz; Athar Hussain; Muhammad Rizwan; Shazia Arif; Saira Ishaq; Shahnaz Zakia; Asmaa M. Abushady; Itoh Kimiko; Kotb A. Attia (Brazilian Journal of Botany, 2023)

Green synthesis of a mesoporous hyper-cross-linked polyamide/polyamine 3D network through Michael addition for the treatment of heavy metals and organic dyes contaminated wastewater - Abdul Waheed; Muhammad Sajid; Mohammad Asif (Chemosphere, 2023)

Melatonin-induced development of adventitious roots, biosynthesis of secondary cell products and greener synthesis of silver nanoparticles for biological activities using Indigofera heterantha - Irfan Ullah; Muhammad Sajid; Nisar Ahmad; Naveed Ahmad; Kamran Rauf; Rabia Khalil; Babar Iqbal; Mazhar Ali; Marcelo Carvalho Minhoto Teixeira Filho; Mohammad K. Okla; Hamada AbdElgawad; Asghar Khan; et al. (South African Journal of Botany, 2023)

Thin-film nanocomposite membranes for efficient removal of emerging pharmaceutical organic contaminants from water - Asif Matin; Nadeem Baig; Deepak Anand; Irshad Ahmad; Muhammad Sajid; Muhammad Saqib Nawaz (Environmental Research, 2023)

Co-occurrence of mycotoxins and other fungal metabolites in total mixed rations of cows from dairy farms in Punjab, Pakistan - Felipe Penagos-Tabares; Mubarik Mahmood; Muhammad Zafar Ullah Khan; Hafiz Muhammad Amjad Talha; Muhammad Sajid; Kanwal Rafique; Saima Naveed; Johannes Faas; Juan Ignacio Artavia; Michael Sulyok; Anneliese Müller; Rudolf Krska; et al. (Mycotoxin Research, 2023)
After India and the USA, Pakistan is the third country leading in global dairy production, a sector of very high socioeconomic relevance in Asia. Mycotoxins can affect animal health, reproduction and productivity. This study analysed a broad range of co-occurring mycotoxins and fungal secondary metabolites derived from Alternaria , Aspergillus , Fusarium , Penicillium and other fungal species. To complete this, a validated multi-metabolite liquid chromatography/electrospray ionization-tandem mass spectrometric (LC/ESI–MS/MS) method was employed, detecting 96 of > 500 tested secondary fungal metabolites. This first preliminary study demonstrated that total mixed rations (TMRs) ( n = 30) from big commercial dairy cattle farms (> 200 lactating cows) in Punjab, Pakistan, presented ubiquitous contamination with mixtures of mycotoxins. The mean of mycotoxins per sample was 14, ranging from 11 to 20 mycotoxins among all TMR samples. Metabolites derived from other fungi and Fusarium spp. showed the highest levels, frequency and diversity among the detected fungal compounds. Among the most prevalent mycotoxins were Fusarium toxins like fumonisins B1 (FB1) (93%), B2 (FB2) (100%) and B3 (FB3) (77%) and others. Aflatoxin B1 (AFB1) was evidenced in 40% of the samples, and 7% exceeded the EU maximum limit for feeding dairy cattle (5 µg/kg at 88% dry matter). No other mycotoxin exceeds the EU guidance values (GVs). Additionally, we found that dietary ingredients like corn grain, soybean meal and canola meal were related to increased contamination of some mycotoxins (like FB1, FB2 and FB3) in TMR from the province of Punjab, Pakistan. Among typical forage sources, the content of maize silage was ubiquitous. Individually, the detected mycotoxins represented relatively low levels. However, under a realistic scenario, long-term exposure to multiple mycotoxins and other fungal secondary metabolites can exert unpredictable effects on animal health, reproduction and productivity. Except for ergot alkaloids (73%), all the groups of metabolites (i.e. derived from Alternaria spp., Aspergillus spp., Fusarium spp., Penicillium spp. and other fungi) occurred in 100% of the TMR samples. At individual levels, no other mycotoxins than AFB1 represented a considerable risk; however, the high levels of co-occurrence with several mycotoxins/metabolites suggest that long-term exposure should be considered because of their potential toxicological interactions (additive or synergistic effects).

Modeling future urban network capacity and land use/land cover simulation using GEE and remote sensing data - Muhammad Nabeel Khalid; Muhammad Nasar Ahmad; Muhammad Asif Javed; Sajid Rashid Ahmad (Arabian Journal of Geosciences, 2023)

Evaluating the influence of green growth, institutional quality and financial inclusion on financial stability: evidence by sustainable finance theory - Muhammad Sajid; Muhammad Akbar Ali Ansari; Arsalan Tanveer; Muhammad Faheem; Asim Waseem (Environmental Science and Pollution Research, 2023)

Foliar architecture differentially restrains metal sequestration capacity in wheat grains (Triticum aestivum L.) grown in hyper-chloride-contaminated soils - Muhammad Sajid Aqeel Ahmad; Mansoor Hameed; Muhammad Kaleem; Sana Fatima; Farooq Ahmad; Muhammad Farooq; Mehtab Maratib; Iqra Aziz (Environmental Science and Pollution Research, 2023)

An efficient virus-induced gene silencing of PDS gene in Solanum lycopersicum (cv. Rio Grande) and its functional analysis - Iqra Mehboob; Muhammad Mughees; Ayesha Baig; Shaukat Ali; Yasar Sajjad; Shahid Iqbal; Zahoor Hussain; Sajid Fiaz; Farhat Abbas; Kotb A. Attia; Asmaa M. Abushady; Mohammad Maroof Shah (Brazilian Journal of Botany, 2023)

Exogenous melatonin mitigates chilling injury in zucchini fruit by enhancing antioxidant system activity, promoting endogenous proline and GABA accumulation, and preserving cell wall stability - Sajid Ali; Aamir Nawaz; Safina Naz; Maratab Ali; Shaghef Ejaz; Muhammad Azam; Kashif Razzaq (Postharvest Biology and Technology, 2023)

Synergistic neuroprotection by phytocompounds of Bacopa monnieri in scopolamine-induced Alzheimer’s disease mice model - Shehla Shoukat; Muhammad Amir Zia; Muhammad Uzair; Roua A. Alsubki; Kaynat Sajid; Sana Shoukat; KOTB A. Attia; Sajid Fiaz; Shaukat Ali; Itoh Kimiko; Ghulam Muhammad Ali (Molecular Biology Reports, 2023)

Arsenic fractionation and speciation in different textured soils supplied with farmyard manure and accumulation by sunflower under alkaline calcareous conditions - Muhammad Awais Piracha; Muhammad Ashraf; Sher Muhammad Shahzad; Sajid Masood; Naeem Akhtar; Rizwana Kausar; Awais Shakoor (Environmental Science and Pollution Research, 2023)

Alleviation of arsenic toxicity-induced oxidative stress in lemon grass by methyl jasmonate - Khansa Saleem; Muhammad Ahsan Asghar; Hafiz Hassan Javed; Ali Raza; Mahmoud F. Seleiman; Abd Ullah; Altafur Rahman; Sufyan Iqbal; Aamir Hanif; Shakeel Imran; Sajid Mahmood Nadeem; Junbo Du; et al. (South African Journal of Botany, 2023)

Progress in genome-wide identification of RBPs and their role in mitigating stresses, and growth in plants - Muhammad Haroon; Hala Tariq; Rabail Afzal; Muhammad Anas; Shanza Nasar; Neha Kainat; Sajid Fiaz; Uswa Irfan; Fahad Idrees; Muhammad Mubashar Zafar (South African Journal of Botany, 2023)

Seed priming with nano-silica effectively ameliorates chromium toxicity in Brassica napus - Zaid Ulhassan; Su Yang; Di He; Ali Raza Khan; Abdul Salam; Wardah Azhar; Sajid Muhammad; Skhawat Ali; Yasir Hamid; Imran Khan; Mohamed Salah Sheteiwy; Weijun Zhou (Journal of Hazardous Materials, 2023)

Comprehensive insights into the regulatory mechanisms of lncRNA in alkaline-salt stress tolerance in rice - Obaid Ur Rehman; Muhammad Uzair; Muhammad Shahbaz Farooq; Bilal Saleem; Safira Attacha; Kotb A. Attia; Umer Farooq; Sajid Fiaz; Wael. H. El-Kallawy; Itoh Kimiko; Muhammad Ramzan Khan (Molecular Biology Reports, 2023)

ADU-Net: Semantic segmentation of satellite imagery for land cover classification - Muhammad Talha; Farrukh A. Bhatti; Sajid Ghuffar; Hamza Zafar (Advances in Space Research, 2023)

Physical properties of multifunctional TM-doped ZnO nanorods and their photocatalytic and anti-bacterial activities - Yasir Zaman; Muhammad Zahid Ishaque; Yasir Yousaf; Muhammad Shahzad; Abu Bakar Siddique; Muhammad Imran Arshad; Muhammad Sajid; Nisar Ali; Ghulam Nabi (Environmental Science and Pollution Research, 2023)

Major challenges in widespread adaptation of aerobic rice system and potential opportunities for future sustainability - Muhammad Shahbaz Farooq; Hira Fatima; Obaid Ur Rehman; Muhammad Yousuf; Rabia Kalsoom; Sajid Fiaz; Muhammad Ramzan Khan; Muhammad Uzair; Shuhao Huo (South African Journal of Botany, 2023)

Exogenous Application of Melatonin Improves the Growth and Productivity of Two Broccoli (Brassica oleracea L.) Cultivars Under Salt Stress - Hasan Sardar; Muhammad Arif Ramzan; Safina Naz; Sajid Ali; Shaghef Ejaz; Riaz Ahmad; Muhammad Ahsan Altaf (Journal of Plant Growth Regulation, 2023)

Anti-inflammatory mechanisms of eucalyptol rich Eucalyptus globulus essential oil alone and in combination with flurbiprofen - Bushra Arooj; Sajid Asghar; Mohammad Saleem; Syed Haroon Khalid; Muhammad Asif; Tahir Chohan; Ikram Ullah Khan; Hafiz Muhammad Zubair; Hafiza Sidra Yaseen (Inflammopharmacology, 2023)

A systematic review on the bioremediation of metal contaminated soils using biochar and slag: current status and future outlook - Sajid Mehmood; Waqas Ahmed; Juha M. Alatalo; Mohsin Mahmood; Rana Muhammad Ammar Asghar; Muhammad Imtiaz; Naseer Ullah; Wei-dong Li; Allah Ditta (Environmental Monitoring and Assessment, 2023)

Asymmetric nexus between financial inclusion and environmental quality: the case of 10 most polluted economies - Sajid Ali; Muhammad Khalid Anser (Environmental Monitoring and Assessment, 2023)

Diversity in Elemental Content in Selected Artemisia L. (Asteraceae) Species from Gilgit-Baltistan Region of Pakistan Based on Inductively Coupled Plasma Atomic Emission Spectrophotometry (ICP-AES) - Adil Hussain; Muhammad Sajid; Daniel Potter; Hassam Rasheed; Mujtaba Hassan; Naeem Akhtar; Bashir Ahmad; Syed Ali Imran Bokhari (Biological Trace Element Research, 2023)

Variations in cold flow and physical properties of Northern Pakistan gas condensate oil after interacting with different polymeric drilling mud systems - Shaine Mohammadali Lalji; Syed Imran Ali; Sajid Hussain; Syed Muhammad Ali; Zeeshan Ali Lashari (Arabian Journal of Geosciences, 2023)

Magnetic layered double hydroxide-based composites as sustainable adsorbent materials for water treatment applications: Progress, challenges, and outlook - Muhammad Sajid; Ihsanullah Ihsanullah (Science of The Total Environment, 2023)

Endocrine disrupting compounds in the baby's world - A harmful environment to the health of babies - Justyna Płotka-Wasylka; Ewa Mulkiewicz; Hanna Lis; Klaudia Godlewska; Aleksandra Kurowska-Susdorf; Muhammad Sajid; Dimitra Lambropoulou; Natalia Jatkowska (Science of The Total Environment, 2023)

“Retraction notice to Carveol ameliorates mercury-induced oxidative stress, neuroinflammation, and neurodegeneration in a mouse brain” NeuroToxicology 92 (2022) 212–226 - Abdullah Alattar; Arooj Mohsin Alvi; Sajid Rashid; Nadia Hussain; Mehreen Gul; Muhammad Ikram; Atif Ali Khan Khalil; Reem Alshaman; Fawad Ali Shah; Shupeng Li; Jingbo Li (NeuroToxicology, 2023)

Removal of pharmaceutically active compounds from water sources using nanofiltration and reverse osmosis membranes: Comparison of removal efficiencies and in-depth analysis of rejection mechanisms - Asif Matin; Shehzada Muhammad Sajid Jillani; Umair Baig; I. Ihsanullah; Khalid Alhooshani (Journal of Environmental Management, 2023)

Machine learning - a novel approach to predict the porosity curve using geophysical logs data: An example from the Lower Goru sand reservoir in the Southern Indus Basin, Pakistan - Wakeel Hussain; Miao Luo; Muhammad Ali; Syed Mumtaz Hussain; Sajid Ali; Sartaj Hussain; Asim Falak Naz; Saddam Hussain (Journal of Applied Geophysics, 2023)

Soil organic carbon sequestration and modeling under conservation tillage and cropping systems in a rainfed agriculture - Sana ur Rehman; Shahzada Sohail Ijaz; Muhammad Ali Raza; Atta Mohi Ud Din; Khalid Saifullah Khan; Shroz Fatima; Taqi Raza; Sajid Mehmood; Amjad Saeed; Muhammad Ansar (European Journal of Agronomy, 2023)

Soil-Root Relationship in a Leaf Succulent Halophyte Suaeda vera from Differently Salt-Affected Habitats - Naila Asghar; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Farooq Ahmad (Water, Air, & Soil Pollution, 2023)

Biochemical profiling of berberine-enriched extract in aluminum chloride induced oxidative damage and neuroinflammation - Muhammad Sajid Hamid Akash; Moazzama Akbar; Kanwal Rehman; Muhammad Ajmal Shah; Pharkphoom Panichayupakaranant; Muhammad Imran; Mohammed A. Assiri (Environmental Science and Pollution Research, 2023)

Cellular and Non-cellular Antioxidant Properties of Vitamin E–Loaded Metallic-Quercetin/Polycaprolactone Nanoparticles for the Treatment of Melanogenesis - Nasreen Ramzan; Muhammad Azeem; Khalid Mahmood; Shahid Shah; Fazal Rahman Sajid Chughtai; Muhammad Hanif; Nabeela Ameer; Zakia Bashir; Farhan Siddique; Muhammad Qaisar (AAPS PharmSciTech, 2023)

Phytoremediation potential modulated by structural and functional traits in a saline desert halophyte Fagonia indica Burm. f - Nargis Naz; Sana Fatima; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Syed Mohsan Raza Shah; Farooq Ahmad; Majid Anwar; Sana Basharat; Ansa Asghar; Muhammad Ashraf (Environmental Science and Pollution Research, 2023)

Aquaculture sediments amended with biochar improved soil health and plant growth in a degraded soil - Sajid Mehmood; Waqas Ahmed; Mohsin Mahmood; Muhammad Shahid Rizwan; Rana Muhammad Ammar Asghar; Juha M. Alatalo; Muhammad Imtiaz; Muhammad Akmal; Hamada Abdelrahman; Jifu Ma; Esmat F. Ali; Weidong Li; et al. (Marine Pollution Bulletin, 2023)

Multibody constrained dynamics of deepwater Y-method installation system - Naeem Ullah; Menglan Duan; Mac Darlington Uche Onuoha; Asad Syed; Muhammad Sajid; Guomin Sun; Wenda Li (Ocean Engineering, 2023)

Modulation of structural and functional traits in facultative halophyte Salvadora oleoides Decne. For adaptability under hyper-arid and saline environments - Ummar Iqbal; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Nargis Naz; Muhammad Ashraf; Muhammad Kaleem (Journal of Arid Environments, 2023)

Adsorption of Pb(II) from wastewater using a red mud modified rice-straw biochar: Influencing factors and reusability - Waqas Ahmed; Sajid Mehmood; Mohsin Mahmood; Sehrish Ali; Awais Shakoor; Avelino Núñez-Delgado; Rana Muhammad Ammar Asghar; Hongwei Zhao; Wenjie Liu; Weidong Li (Environmental Pollution, 2023)

How Does Health Uncertainty Impact Greenhouse Gas Emissions in European Union Economies? A Blessing in Disguise - Sajid Ali; Muhammad Khalid Anser (International Journal of Environmental Research, 2023)

An overview of genome engineering in plants, including its scope, technologies, progress and grand challenges - Muhammad Sufyan; Umar Daraz; Sajjad Hyder; Usman Zulfiqar; Rashid Iqbal; Sayed M. Eldin; Farzana Rafiq; Naveed Mahmood; Khurram Shahzad; Muhammad Uzair; Sajid Fiaz; Iftikhar Ali (Functional & Integrative Genomics, 2023)

In-field deployable and facile nanosensor for the detection of pesticides residues - Naveed Akhtar Shad; Anam Munawar; Yasir Javed; Allah Rakha; Ahsan Riaz; Salah Ud Din; Iqra Zareef; Muhammad Munir Sajid; Muahmmad Farhan Khan; Sareen Akhtar; Midhat Salman (Analytica Chimica Acta, 2023)

Detrimental effects of Cd and temperature on rice and functions of microbial community in paddy soils - Raheel Munir; Mehmood Jan; Sajid Muhammad; Muhammad Afzal; Nazia Jan; Muhammad Umair Yasin; Iqbal Munir; Aqib Iqbal; Shuaiqi Yang; Weijun Zhou; Yinbo Gan (Environmental Pollution, 2023)

Dramatic changes in anatomical traits of a C4 grass Chrysopogon serrulatus Trin. (Poaceae) over a 1000 m elevational gradient - Sana Fatima; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Majid Anwar; Mahwish Munir; Muhammad Ashraf; Syed Mohsan Raza Shah; Sana Basharat; Iftikhar Ahmad; Sangam Khalil (Journal of Mountain Science, 2023)

Molecularly imprinted ormosil as a sorbent for targeted dispersive solid phase micro extraction of pyriproxyfen from strawberry samples - Muhammad Hayat; Suryyia Manzoor; Hina Raza; Muhammad Imran Khan; Abdallah Shanableh; Muhammad Sajid; Tahani Mazyad Almutairi; Rafael Luque (Chemosphere, 2023)

Editorial overview: Nanomaterials as materials for removal, extraction, sensing, and detection of environmental contaminants - Muhammad Sajid; Sandeep Kumar Verma (Current Opinion in Environmental Science & Health, 2023)

Ameliorative symbiosis of Serratia fonticola (S1T1) under salt stress condition enhance growth-promoting attributes of Cucumis sativus L - Yong-Sun Moon; Murtaza Khan; Muhammad Aaqil Khan; Sajid Ali (Symbiosis, 2023)

Unveiling safflower yield, oil content, water use efficiency, and membrane stability under differential irrigation regimes - Muhammad Sajid; Hassan Munir; Abdul Khaliq; Ghulam Murtaza (Arabian Journal of Geosciences, 2023)

Moving towards sustainability: how do low-carbon energy, current account balance, and reserves induce environmental deterioration in the Big 3? - Mubeen Abdur Rehman; Muhammad Umer Quddoos; Muhammad Sajid Amin; Ghulam Ghouse (Environmental Science and Pollution Research, 2023)

Synthesis of co-polyamide reverse osmosis membrane constituting a linear aliphatic triamine and m-phenylenediamine for enhanced desalination performance - Abdul Waheed; Umair Baig; Asif Matin; Shehzada Muhammad Sajid Jillani; Naef A.A. Qasem; Isam H. Aljundi (Desalination, 2023)

Toxicity and tolerance of nickel in sunflower (Helianthus annuus L.) - Muhammad Sajid Aqeel Ahmad; Alia Riffat; Mumtaz Hussain; Mansoor Hameed; Ambreen Khadija Alvi (Environmental Science and Pollution Research, 2023)

“Ficus johannis Boiss. leaves ethanolic extract ameliorate streptozotocin-induced diabetes in rats by upregulating the expressions of GCK, GLUT4, and IGF and downregulating G6P” - Afshan Asghar; Ali Sharif; Sana Javaid Awan; Bushra Akhtar; Muhammad Furqan Akhtar; Sajid Ali; Shahnaz (Environmental Science and Pollution Research, 2023)

In-situ construction of binder-free MnO2/MnSe heterostructure membrane for high-performance energy storage in pseudocapacitors - Qasim Abbas; Abdul Mateen; Sajid Hussain Siyal; Najam Ul Hassan; Asma A. Alothman; Mohamed Ouladsmane; Sayed M. Eldin; Mohd Zahid Ansari; Muhammad Sufyan Javed (Chemosphere, 2023)

MOF-based membranes for oil/water separation: Status, challenges, and prospects - Mohammad Awwad; Muhammad Bilal; Muhammad Sajid; Muhammad Saqib Nawaz; Ihsanullah Ihsanullah (Journal of Environmental Chemical Engineering, 2023)

Polyetherimide membrane with tunable porous morphology for safe lithium metal-based batteries - Arshad Hussain; Andleeb Mehmood; Adil Saleem; Muhammad K. Majeed; Waseem Raza; Rashid Iqbal; Sajid Rauf; Ali Saad; Yonggui Deng; Geng Luo; Kai Zong; Liu Wei; et al. (Chemical Engineering Journal, 2023)

Evaluating adoption of climate smart agricultural practices among farmers in the Fujian Province, China - Rao Sabir Sattar; Muhammad Sajid Mehmood; Muhammad Hammad Raza; V. P. I. S. Wijeratne; Babar Shahbaz (Environmental Science and Pollution Research, 2023)

Zeolite amendment reduces lead accumulation and improves growth and yield in tomato plants irrigated with sewage water - Rashid Jawad; Aamir Nawaz; Shaghef Ejaz; Sajid Ali; Muhammad Shahzad Saleem; Hafiz Mohkum Hammad (Environmental Science and Pollution Research, 2023)

Application of silver nanoparticles synthesized through varying biogenic and chemical methods for wastewater treatment and health aspects - Asima Rasheed; Sabir Hussain; Waseem Mushtaq; Muhammad Zubair; Khadija Siddique; Kotb Attia; Naeem Khan; Sajid Fiaz; Farrukh Azeem; Yinglong Chen (Environmental Science and Pollution Research, 2023)

Improving drought mitigation strategies and disaster risk reduction through MODIS and TRMM-based data in relation to climate change over Pakistan - Shahzad Ali; Abdul Basit; Tyan Alice Makanda; Inamullah; Fahim Ullah Khan; Muhammad Sajid; Tamseela Riaz; Hira Farooq Abbasi; Manzoor; Amir Sohail (Environmental Science and Pollution Research, 2023)

Transport infrastructure, economic growth, and transport CO2 emissions nexus: Does green energy consumption in the transport sector matter? - Jiapeng Dai; Rafael Alvarado; Sajid Ali; Zahoor Ahmed; Muhammad Saeed Meo (Environmental Science and Pollution Research, 2023)

Investigating the textural and physico-mechanical response of granites to heat treatment - Hamza Khan; Muhammad Sajid (International Journal of Rock Mechanics and Mining Sciences, 2023)

Electrically conductive Pt-MOFs for acidic oxygen reduction: Optimized performance via altering conjugated ligands - Rashid Iqbal; Sajjad Ali; Adil Saleem; Muhammad K. Majeed; Arshad Hussain; Sajid Rauf; Abdul Rehman Akbar; Hu Xu; Liang Qiao; Wei Zhao (Chemical Engineering Journal, 2023)

Downregulation of NF-κB activation pathways using essential oil derived from Citrus pseudolimon: Anticancer and anti-inflammatory potential - Arfaa Sajid; Qaisar Manzoor; Anam Sajid; Arif Nazir; Muhammad Arsalan Mumtaz; Najum Fatima; Samar Zuhair Alshawwa; Munawar Iqbal; Umer Younas (Biocatalysis and Agricultural Biotechnology, 2023)

Genome mining, antimicrobial and plant growth-promoting potentials of halotolerant Bacillus paralicheniformis ES-1 isolated from salt mine - Sajid Iqbal; Muhammad Qasim; Hazir Rahman; Naeem Khan; Rehan Zafar Paracha; Muhammad Faraz Bhatti; Aneela Javed; Hussnain Ahmed Janjua (Molecular Genetics and Genomics, 2023)

Occurrence and Distribution of Heavy Metals in Mining Degraded Soil and Medicinal Plants: A Case Study of Pb/Zn Sulfide Terrain Northern Areas, Pakistan - Javed Nawab; Muhammad Idress; Sajid Ullah; Gul Rukh; Rimsha Zainab; Hassan Sher; Junaid Ghani; Sardar Khan; Zahid Ullah; Imran Ahmad; Syed Weqas Ali (Bulletin of Environmental Contamination and Toxicology, 2023)

Invasive success of Ipomoea carnea Jacq. through plasticity in physio-anatomical and phytochemical traits across diversified habitats - Syed Mohsan Raza Shah; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Muhammad Ashfaq Wahid (Biological Invasions, 2023)

Remote sensing strategies to monitoring land use maps with AVHRR and MODIS data over the South Asia regions - Shahzad Ali; Huang An Qi; Malak Henchiri; Zhang Sha; Fahim Ullah Khan; Muhammad Sajid; Jiahua Zhang (Environmental Science and Pollution Research, 2022)

Sedimentology and diagenesis control on reservoir quality of Sheikhan Limestone (Eocene) at the Panoba and Sheikhan Nala Section, Kohat Basin, Pakistan - Atif Salim; Muhammad Kashif; Bin Dou; Danish Khan; Muhammad Jawad Munawar; Noor Ahmed; Naveed Rehman; Muhammad Sajid; Zahid Ullah; Muhammad Tariq (Carbonates and Evaporites, 2022)

Evaluating the thermal-cooling induced effects on the Ambela granite properties (from Pakistan) using experimental and image processing techniques - Naseer Muhammad Khan; Liqiang Ma; Kewang Cao; Sajjad Hussain; Asghar Ali; Wei Liu; Saad S. Alarifi; Kausar Sultan shah; Sajid Khan; Yang Xiaoxu; Yujun Xu (Bulletin of Engineering Geology and the Environment, 2022)

The long-term dynamic relationship between communicable disease spread, economic prosperity, greenhouse gas emissions, and government health expenditures: preparing for COVID-19-like pandemics - Muhammad Jawad Sajid; Syed Abdul Rehman Khan; Yubo Sun; Zhang Yu (Environmental Science and Pollution Research, 2022)

Screening, Characterization and Optimization of Bioactive Peptides with Antibacterial Activities Against Multi-Drug Resistant Pathogens, Produced by Bacillus safensis Strain MK-12.1 - Sajid Iqbal; Farida Begum; Muhammad Qasim (International Journal of Peptide Research and Therapeutics, 2022)

Application of RNAi technology: a novel approach to navigate abiotic stresses - Izhar Ullah; Ehab A. R. Kamel; Syed Tanveer Shah; Abdul Basit; Heba I. Mohamed; Muhammad Sajid (Molecular Biology Reports, 2022)

Waste management and green technology: future trends in circular economy leading towards environmental sustainability - Muhammad Tanveer; Syed Abdul Rehman Khan; Muhammad Umar; Zhang Yu; Muhammad Jawad Sajid; Ikram Ul Haq (Environmental Science and Pollution Research, 2022)

Evaluation of unconventional hydrocarbon reserves using petrophysical analysis to characterize the Yageliemu Formation in the Yakela gas condensate field, Tarim Basin, China - Wakeel Hussain; Lin Pan; Xiao Wang; Muhammad Saqlain; Muhammad Ali; Rakhshanda Sadaf; Nafees Ali; Irshad Hussain; Sajid Ali; Mazahir Hussain; Ali Asghar (Arabian Journal of Geosciences, 2022)

Evaluation of agro-morphological traits, seed characterization and genetic diversity of local rice (Oryza sativa L.) varieties of Pakistan - Urooj Fazal; Israr Ud Din; Amir Muhammad Khan; Fahim Ullah Khan; Mudassar Nawaz Khan; Navid Iqbal; Muhammad Ibrahim; Sajid Ali Khan Bangash (Genetic Resources and Crop Evolution, 2022)

Exploring thiazole-linked thioureas using alkaline phosphatase assay, biochemical evaluation, computational analysis and structure–activity relationship (SAR) studies - Sajid Ali Channar; Pervaiz Ali Channar; Aamer Saeed; Aisha A. Alsfouk; Syeda Abida Ejaz; Rabail Ujan; Razia Noor; Muhammad Sajjad Bilal; Qamar Abbas; Zahid Hussain; Bilal Ahmad Khan; Hussain Raza; et al. (Medicinal Chemistry Research, 2022)

Yttrium Doped Bismuth Vanadate Titania Heterojunction for Efficient Photoreduction of Cr from Wastewater Under Visible Light - Uswa Zahoor; Muhammad Imran Rameel; Ahad Hussain Javed; Muhammad Abdullah Khan; Jehan Y. Al-Humaidi; Sajid Iqbal; Afrah Mohammed Aldawsari; Afzal Shah (International Journal of Environmental Research, 2022)

Identifying contributing factors to China’s declining share of renewable energy consumption: no silver bullet to decarbonisation - Muhammad Jawad Sajid; Syed Abdul Rehman Khan; Ernesto D. R. Santibanez Gonzalez (Environmental Science and Pollution Research, 2022)

Countrywide inter‐epidemic region migration pattern suggests the role of southwestern population in wheat stripe rust epidemics in China - Muhammad Awais; Sajid Ali; Meng Ju; Wei Liu; Gensheng Zhang; Zedong Zhang; Zejian Li; Xinyao Ma; Lin Wang; Zhimin Du; Xiaxia Tian; Qingdong Zeng; et al. (Environmental Microbiology, 2022)
Understanding countrywide pathogen population structure and inter‐epidemic region spread is crucial for deciphering crop potential losses. Wheat stripe rust caused by Puccinia striiformis f. sp. tritici is a destructive disease that affects worldwide wheat production, widespread in China, representing largest epidemic region globally. This study aimed to understand the population structure and migration route of P . striiformis f. sp. tritici across China based on sampling from 15 provinces representing six epidemic zones, viz., over‐summering, over‐wintering, eastern, Yun‐Gui, Xinjiang and Tibet epidemic regions. High genotypic diversity was recorded in over‐summering, Tibet and over‐wintering epidemic regions. Epidemic regions partly explain population subdivision with variable divergence ( F ST = 0.005–0.344). Xinjiang and Tibet epidemic regions were independent epidemic zones with least sharing of genotypes. Among other epidemic zones, i.e. over‐summering, over‐wintering, eastern and Yun‐Gui epidemic zones, re‐sampling MLGs, clustering‐based structure, DAPC analyses, relative migration and low divergence ( F ST from 0.006 to 0.073) revealed frequent geneflow. Yun‐Gui epidemic regions, with a potential for both over‐summering and over‐wintering, could play an important role in causing epidemics in main wheat‐cultivating areas of China. High diversity, recombination signatures and inter‐epidemic region migration patterns need to be considered in host‐resistant cultivar development in China and neighbouring countries, considering risk of long‐distance migration capacity of pathogen.

Impact assessment of drought monitoring events and vegetation dynamics based on multi-satellite remote sensing data over Pakistan - Shahzad Ali; Abdul Basit; Jian Ni; Manzoor; Fahim Ullah Khan; Muhammad Sajid; Muhammad Umair; Tyan Alice Makanda (Environmental Science and Pollution Research, 2022)

Differential neuroprotective effect of curcuminoid formulations in aluminum chloride–induced Alzheimer’s disease - Anam Shabbir; Kanwal Rehman; Muhammad Sajid Hamid Akash; Moazzama Akbar; Zunera Chaudhary; Pharkphoom Panichayupakaranant; Muhammad Ajmal Shah (Environmental Science and Pollution Research, 2022)

Re-examining the nexuses of communicable diseases, environmental performance, and dynamics of sustainable Development in OECD countries - Zhang Yu; Muhammad Umer Quddoos; Muhammad Hanif Akhtar; Muhammad Sajid Amin; Laeeq Razzak; Muhammad Tariq; Syed Abdul Rehman Khan (Environmental Science and Pollution Research, 2022)

Contribution of structural and functional adaptations of hyper-accumulator Suaeda vera Forssk. ex J.F. Gmel. for adaptability across salinity gradients in hot desert - Nargis Naz; Sana Fatima; Mansoor Hameed; Muhammad Ashraf; Muhammad Sajid Aqeel Ahmad; Farooq Ahmad; Syed Mohsan Raza Shah; Faakeha Islam; Iftikhar Ahmad; Farial Ejaz; Mehwish Naseer (Environmental Science and Pollution Research, 2022)

Extracellular vesicles and exosome: insight from physiological regulatory perspectives - Muhammad Yasir Waqas; Muhammad Arshad Javid; Muhammad Mudasser Nazir; Nasir Niaz; Muhammad Farrukh Nisar; Zahid Manzoor; Sheraz Ahmed Bhatti; Sajid Hameed; Muhammad Haseeb Khaliq (Journal of Physiology and Biochemistry, 2022)

Temperature-Dependent Speciation Analysis of Chromium Immobilized in Calcium Hydroxyapatite Matrix - Sajid Iqbal; Yasir Faiz; Messaoud Harfouche; Muhammad Saifullah; Jong-Il Yun (International Journal of Environmental Research, 2022)

Biochemical profiling of lead-intoxicated impaired lipid metabolism and its amelioration using plant-based bioactive compound - Abdul Qader; Kanwal Rehman; Muhammad Sajid Hamid Akash (Environmental Science and Pollution Research, 2022)

Dynamic common correlated effects of pandemic uncertainty on environmental quality: fresh insights from East-Asia and Pacific countries - Zhen Liu; Ping Pang; Wei Fang; Sajid Ali; Muhammad Khalid Anser (Air Quality, Atmosphere & Health, 2022)

Decomposition analytics of carbon emissions by cement manufacturing – a way forward towards carbon neutrality in a developing country - Rizwan Rasheed; Fizza Tahir; Muhammad Afzaal; Sajid Rashid Ahmad (Environmental Science and Pollution Research, 2022)

Arsenic contamination, induced symptoms, and health risk assessment in groundwater of Lahore, Pakistan - Habib Ur Rehman; Saeed Ahmed; Mujeeb Ur Rahman; Muhammad Sajid Mehmood (Environmental Science and Pollution Research, 2022)

Sargassum wightii Aqueous Extract Improved Salt Stress Tolerance in Abelmoschus esculentus by Mediating Metabolic and Ionic Rebalance - Zawar Khan; Humaira Gul; Mamoona Rauf; Muhammad Arif; Muhammad Hamayun; Aziz Ud-Din; Zahoor Ahmad Sajid; Sheza Ayaz Khilji; Aliya Rehman; Asma Tabassum; Zahida Parveen; In-Jung Lee (Frontiers in Marine Science, 2022)
Salinity stress has hindered the growth and yield of crops globally. The demands for inducing salt stress tolerance by natural and biological sources with potent antioxidants and growth-promoting metabolites have been the main focus of the recent era. Therefore, the current research was conducted to extract salt stress tolerance-ameliorating metabolites and growth-promoting hormones from the marine brown macroalgae Sargassum wightii Greville ex J. Agardh with maximum antioxidant potential used as a liquid fertilizer for okra ( Abelmoschus esculentus L.). In the current study, the biochemical analysis showed that Sargassum aqueous extract (SAE) was rich in growth-promoting metabolites, antioxidants, and hormones. Meanwhile, overaccumulation of glycine betaine attracted the focus of the current research dealing with salt stress tolerance amelioration in A. esculentus . The plants supplemented with SAE (2% and 4%) and 0.04% ascorbic acid (AsA) alone and in combinations were subjected to sodium salt stress (NaCl; 75 mM). Results revealed that SAE efficiently promoted the vegetative and reproductive growth of plants by elevating the growth-promoting metabolites and hormones in comparison to control plants. Ionic contents (Na + , K + , Ca 2+ , and Mg 2+ ) and ratios (K + /Na + , Mg 2+ /Na + , and Ca 2+ /Na + ) were modulated in SAE-treated plants. SAE also increased the level of carbohydrates, proteins, lipids, carotenoids, and proline and decreased the level of hydrogen peroxide and abscisic acid in salt-treated plants compared with the control groups. Enzymatic activities of catalase, ascorbate peroxidase, and guaiacol peroxidase were also enhanced by SAE treatment upon salt stress. The SAE-mediated stress tolerance amelioration and the positive growth response of A. esculentus were further accelerated by AsA (0.04%) supplementation used in combination with SAE (2% and 4%). The current study revealed a novel report of the antioxidant and metabolite-rich algal extract ( S. wightii ) formulation along with AsA that induced salt stress tolerance and promoted the overall growth performance of A. esculentus by rebalancing the ionic and metabolic status.

Unraveling the survival potential of a desert halophyte Salvadora oleoides Decne. across heterogenic environments - Ummar Iqbal; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf (Trees, 2022)

MiRNA fine tuning for crop improvement: using advance computational models and biotechnological tools - Asad Abbas; Adnan Noor Shah; Mohsin Tanveer; Waseem Ahmed; Anis Ali Shah; Sajid Fiaz; Muhammad Mohsin Waqas; Sami Ullah (Molecular Biology Reports, 2022)

Molecular cloning, characterization and expression analysis of two 12-oxophytodienoate reductases (NtOPR1 and NtOPR2) from Nicotiana tabacum - Feiyan Huang; Farhat Abbas; Dylan O’Neill Rothenberg; Muhammad Imran; Sajid Fiaz; Naveed ur Rehman; Sikandar Amanullah; Afifa Younas; Yan Ding; Xianjie Cai; Xiaolong Chen; Lei Yu; et al. (Molecular Biology Reports, 2022)

Characterization of functional genes GS3 and GW2 and their effect on the grain size of various landraces of rice (Oryza sativa) - Haroon Rasheed; Sajid Fiaz; Muhammad Abid Khan; Sultan Mehmood; Faizan Ullah; Sumbul Saeed; Shahid Ullah Khan; Tabassam Yaseen; Reem M. Hussain; Abdul Qayyum (Molecular Biology Reports, 2022)

Comprehensive characterization of Guanosine monophosphate synthetase in Nicotiana tabacum - Feiyan Huang; Farhat Abbas; Sajid Fiaz; Muhammad Imran; Ke Yanguo; Waseem Hassan; Umair Ashraf; Yuansheng He; Xuanjie Cai; Zhijiang Wang; Lei Yu; Xianwen Ye; et al. (Molecular Biology Reports, 2022)

ATP-binding cassette transporters expression profiling revealed its role in the development and regulating stress response in Solanum tuberosum - Madiha Zaynab; Zongkang Wang; Athar Hussain; Khalida Bahadar; Mateen Sajid; Yasir Sharif; Muhammad Azam; Kalsoom Sughra; Muhammad Ammar Raza; Khalid Ali Khan; Shuangfei Li (Molecular Biology Reports, 2022)

Geochemical characteristics of coal seams within the Paleocene Patala Formation, Central Salt Range coal mines (Punjab), Northern Pakistan - Muhammad Sajid; Natasha Khan; Faisal Shah; Muhammad Kashif; Shaukat Khan (Journal of Sedimentary Environments, 2022)

Phycoremediation of textile effluents with enhanced efficacy of biodiesel production by algae and potential use of remediated effluent for improving growth of wheat - Muhammad Rashid Waqas; Sajid Mahmood Nadeem; Muhammad Yahya Khan; Zeeshan Ahmad; Liaqat Ali; Hafiz Naeem Asghar; Azeem Khalid (Environmental Science and Pollution Research, 2022)

Porostereum spadiceum-AGH786 Regulates the Growth and Metabolites Production in Triticum aestivum L. Under Salt Stress - Syeda Leeda Gul; Yong-Sun Moon; Muhammad Hamayun; Sumera Afzal Khan; Amjad Iqbal; Muhammad Aaqil Khan; Anwar Hussain; Maryam Shafique; Yoon-Ha Kim; Sajid Ali (Current Microbiology, 2022)

Exploring the potential of Eocene carbonates through petrographic, geochemical, and geotechnical analyses for their utilization as aggregates for engineering structures - Abdul Rahim Asif; Ihtisham Islam; Waqas Ahmed; Muhammad Sajid; Adnan Qadir; Allah Ditta (Arabian Journal of Geosciences, 2022)

Survival strategies in two high altitude Sorghum species from western Himalayas - Khwaja Shafique Ahmad; Anum Javaid; Mansoor Hameed; Sana Fatima; Farooq Ahmad; Muhammad Ashraf; Syed Mohsan Raza Shah; Muhammad Sajid Aqeel Ahmad; Iftikhar Ahmad (Acta Physiologiae Plantarum, 2022)

Anatomical and physiological features modulate ion homeostasis and osmoregulation in aquatic halophyte Fimbristylis complanata (Retz.) link - Muhammad Kaleem; Mansoor Hameed; Farooq Ahmad; Muhammad Ashraf; Muhammad Sajid Aqeel Ahmad (Acta Physiologiae Plantarum, 2022)

Temporal variation in leachate composition of a newly constructed landfill site in Lahore in context to environmental pollution and risks - Mahsoon Ashraf; Muhammad Zeshan; Sadia Hafeez; Rahib Hussain; Abdul Qadir; Muzaffar Majid; Farman Ahmad; Sajid Rashid Ahmad (Environmental Science and Pollution Research, 2022)

Endophytic aspergillus oryzae reprograms Abelmoschus esculentus L. to higher growth under salt stress via regulation of physiochemical attributes and antioxidant system - Farzana Gul Jan; Nusrat bibi; Muhammad Hamayun; Yong-Sun Moon; Gul Jan; Maryam Shafique; Sajid Ali (Biologia, 2022)

Asymmetric openness-environment nexus in most open OIC countries: new evidence from quantile-on-quantile (QQ) estimation - Sajid Ali; Zulkornain Yusop; Muhammad Saeed Meo (Environmental Science and Pollution Research, 2022)

Preparation and Quality Attributes of Egg-reduced Pound Cake Incorporating Grass Carp ( Ctenopharyngodonidella ) Protein Concentrate - Sohail Khan; Haroon Shah; Sajid Kamal; Abdur Rehman; Qayyum Shehzad; Umer Karamat; Aiman Karim; Mudassar Hussain; Muhammad Muneeb; Wenshui Xia (Journal of Aquatic Food Product Technology, 2022)

Range extension and species confirmation of Rhyneptesicus nasutus (Sind Serotine Bat) (Mammalia:Chiroptera) from Bajaur Agency, FATA, Pakistan - Muhammad Idnan; Sajid Mansoor; Muhammad Babar Khawar; Arshad Javid; Ali Hussain; Muhammad Imran; Arif Ullah (Molecular Biology Reports, 2022)

Modulation in Plant Micro-structures Through Soil Physicochemical Properties Determines Survival of Salsola imbricata Forssk. in Hypersaline Environments - Nargis Naz; Sana Fatima; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Hina Shahid; Ummar Iqbal; Muhammad Kaleem; Syed Mohsan Raza Shah; Iftikhar Ahmad (Journal of Soil Science and Plant Nutrition, 2022)

A review on sources of heavy metals, their toxicity and removal technique using physico-chemical processes from wastewater - Muhammad Rafique; Syeda Hajra; Muhammad Bilal Tahir; Syed Sajid Ali Gillani; Muneeb Irshad (Environmental Science and Pollution Research, 2022)

Characterization and thermal behavior of marble from northwestern Pakistan - Atta Ur Rehman; Waqas Ahmed; Shahid Azam; Muhammad Sajid (Innovative Infrastructure Solutions, 2022)

Bio-diesel production of sunflower through sulphur management in a semi-arid subtropical environment - Athar Mahmood; Masood Iqbal Awan; Sana Sadaf; Ahmed Mukhtar; Xiukang Wang; Sajid Fiaz; Sher Aslam Khan; Habib Ali; Faran Muhammad; Zafar Hayat; Farhana Gul; Shah Fahad (Environmental Science and Pollution Research, 2022)

A Review of Antimicrobial Peptides: Its Function, Mode of Action and Therapeutic Potential - Sehrish Nayab; Muhammad Aamir Aslam; Sajjad ur Rahman; Zia ud Din Sindhu; Sanaullah Sajid; Nishat Zafar; Maida Razaq; Rabia Kanwar; Amanullah (International Journal of Peptide Research and Therapeutics, 2022)

Ecofriendly application of coconut coir (Cocos nucifera) extract for silk dyeing - Shahid Adeel; Shumaila Kiran; Muhammad Shahid; Sajid Raza Habib; Noman Habib; Muhammad Hussaan (Environmental Science and Pollution Research, 2022)

Response of root development and nutrient uptake of two chinese cultivars of hybrid rice to nitrogen and phosphorus fertilization in Sichuan Province, China - Guotao Yang; Farhan Nabi; Sumbal Sajid; Abdul Rasheed Kaleri; Ali Murad Jakhar; Liang Cheng; Martin Raspor; Noor Muhammad; Jun Ma; Yungao Hu (Molecular Biology Reports, 2021)
Background Chemical fertilization helped modern agriculture in grain yield improvement to ensure food security. The response of chemical fertilization for higher hybrid rice production is highly dependent on optimal fertilization management in paddy fields. To assess such responses, in the current work we examine the yield, root growth, and expression of related genes responsible for stress metabolism of nitrogen (N) and phosphorus (P) in two hybrid-rice cultivars Deyou4727 (D47) and Yixiangyou2115 (Y21). Methods and results The experiment followed four nitrogen (N) (N 0 , N 60 , N 120, and N 180 kg/ha) and phosphorus (P) (P 0 , P 60 , P 90 , and P 120 kg/ha) fertilizer levels. The grain yield in D47 was more sensitive to nitrogen application, while Y21 was more sensitive to phosphorus application, which resulted in comparatively higher biomass and yield. Our findings were corroborated by gene expression studies of glutamine synthetase OsGS1;1 and OsGS1;2 and phosphate starvation-related genes PHR1 and SPX , confirming sensitivity to N and P application. The number of roots was less sensitive to nitrogen application in D47 between N 0 and N 60 , but the overall nutrient response difference was significantly higher due to the deep rooting system as compared to Y21. Conclusions The higher yield, high N and P use efficiency, and versatile root growth of D47 make it suitable to reduce unproductive usage of N and P from paddy fields, improving hybrid rice productivity, and environmental safety in the Sichuan basin area of China.

Role of pine wilt disease based on optimal control strategy at multiple scales: A case study of Korea - Muhammad Ozair; Takasar Hussain; Kashif Ali Abro; Sajid Jameel; Aziz Ullah Awan (Journal of Biosciences, 2021)

Analysis of food resources, host availability and insecticidal impacts on the fecundity, longevity and parasitism efficiency of Diaertiella rapae (M’intosh) - Ahmad Nawaz; Habib Ali; Sajid Fiaz; Muhammad Sufyan; Miza Abdul Qayyum; Rashid Azad; Yasir Niaz; Muhamamd Adnan Bodlah; Khalid Ali Khan (International Journal of Tropical Insect Science, 2021)

Genetic basis of some physiological traits and yield in early and late sowing conditions in bread wheat (Triticum aestivum L.) - Mian Abdur Rehman Arif; Maryam Liaqat; Muhammad Imran; Muhammad Qandeel Waheed; Anjuman Arif; Sukhwinder Singh; Sajid Shokat (Journal of Applied Genetics, 2021)

Economic assessment of prospective shale gas play in Pakistan using discounted cashflow model - Faizan Ali; Muhammad Arqam Khan; Naeem ul Hussain Dahraj; Musab Usman; Laiba Sajid Cheema (Arabian Journal of Geosciences, 2021)

Correction to: First report of Alternaria alternata causing post‑harvest brown spot of Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Muhammad Naveed Aslam; Tanvir Ahmad; Ambreen Maqsood; Muhammad Shafique (Journal of Plant Pathology, 2021)

First report of Alternaria alternata causing post-harvest brown spot of Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Muhammad Naveed Aslam; Tanvir Ahmad; Ambreen Maqsood; Muhammad Shafique (Journal of Plant Pathology, 2021)

Biochemical investigation of human exposure to aflatoxin M1 and its association with risk factors of diabetes mellitus - Muhammad Sajid Hamid Akash; Muhammad Ejaz ul Haq; Abdul Qader; Kanwal Rehman (Environmental Science and Pollution Research, 2021)

Determinants and implications of environmental practices for waste management and the minimization in the construction industry: a case study of Pakistan - Ahsan Riaz Khan; Allah Ditta; Muhammad Sajid Mehmood; Zheng MaoSheng; Maryam Natalia (Environmental Science and Pollution Research, 2021)

Structural and Functional Determinants of Physiological Pliability in Kyllinga brevifolia Rottb. for Survival in Hyper-Saline Saltmarshes - Sahar Mumtaz; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Iftikhar Ahmad; Muhammad Ashraf; Muhammad Hamzah Saleem (Water, Air, & Soil Pollution, 2021)

Role of nanotechnology in animal production and veterinary medicine - Ahmad Ali; Muhammad Ijaz; Yasir Razzaq Khan; Hina Afzal Sajid; Kashif Hussain; Ameer Hamza Rabbani; Muhammad Shahid; Omer Naseer; Awais Ghaffar; Muhammad Anas Naeem; Muhammad Zeeshan Zafar; Amir Iftikhar Malik; et al. (Tropical Animal Health and Production, 2021)

Population structure and phylogenetic relationship of Peach [Prunus persica (L.) Batsch] and Nectarine [Prunus persica var. nucipersica (L.) C.K. Schneid.] based on retrotransposon markers - Hina Naeem; Faisal Saeed Awan; Peter Michael Dracatos; Muhammad Wasim Sajid; Shahzad Saleem; Qudsia Yousafi; Muhammad Saad Khan; Asim Mehmood; Bushra Zulfiqar (Genetic Resources and Crop Evolution, 2021)

Occurrence, distribution, and pollution indices of potentially toxic elements within the bed sediments of the riverine system in Pakistan - Javed Nawab; Zia Ud Din; Riaz Ahmad; Sardar Khan; Mazhar Iqbal Zafar; Shah Faisal; Waleed Raziq; Hamza Khan; Zia Ur Rahman; Abid Ali; Muhammad Qayash Khan; Sajid Ullah; et al. (Environmental Science and Pollution Research, 2021)

Genetic susceptibility of δ-ALAD associated with lead (Pb) intoxication: sources of exposure, preventive measures, and treatment interventions - Abdul Qader; Kanwal Rehman; Muhammad Sajid Hamid Akash (Environmental Science and Pollution Research, 2021)

Sewage wastewater reclamation with sand column filter and reduction of heavy metal accumulation in tomato and okra - Safina Naz; Muhammad Akbar Anjum; Shaghef Ejaz; Sajid Ali; Bushra Saddiq; Hasan Sardar; Sakeena Tul-Ain Haider (Environmental Science and Pollution Research, 2021)

Sedimentary evolution of middle Jurassic epeiric carbonate ramp Hazara Basin Lesser Himalaya Pakistan - Malik Muhammad Saud Sajid Khan; Qasim Ali Jadoon; Muhammad Umar; Ahsan Ali Khan (Carbonates and Evaporites, 2021)

Low temperature and hypoxic conditions induce flavonoids biosynthesis and enhances antioxidant potential of crabapple (Malus profusion) fruits - Rana Naveed Ur Rehman; Sajid Ali; Mahmood Ul Hasan; Raheel Anwar; Muhammad Wasim Haider; Ahmad Sattar Khan; Aman Ullah Malik; Li Pengmin (Acta Physiologiae Plantarum, 2021)

Bismuth vanadate/MXene (BiVO4/Ti3C2) heterojunction composite: enhanced interfacial control charge transfer for highly efficient visible light photocatalytic activity - Muhammad Munir Sajid; Sadaf Bashir Khan; Yasir Javed; Nasir Amin; Zhengjun Zhang; Naveed Akhtar Shad; Haifa Zhai (Environmental Science and Pollution Research, 2021)

Prevalence of contamination of aflatoxin M1 in milk: a retrospective analysis of studies conducted in Pakistan - Muhammad Sajid Hamid Akash; Kanwal Rehman; Kanwal Irshad (Environmental Monitoring and Assessment, 2021)

Epidemiology of molecular probes in Xpert MTB/RIF assay in Khyber Pakhtunkhwa, Pakistan - Anwar Sheed Khan; Muhammad Tahir Khan; Sajid Ali; Taj Ali Khan; Muhammad Qasim; Arif Malik; Sajid Ali; Wasim Sajjad; Qurrat ul ain; Muhammad Irfan (Archives of Microbiology, 2021)

Phytochemical profiling, in vitro and in vivo anti-inflammatory, analgesic and antipyretic potential of Sesuvium sesuvioides (Fenzl) Verdc. (Aizoaceae) - M. Sajid-ur-Rehman; Saiqa Ishtiaq; Mohsin Abbas Khan; Meshal Alshamrani; Muhammad Younus; Ghazala Shaheen; Muhammad Abdullah; Ghulam Sarwar; Muhammad Sohaib Khan; Faraza Javed (Inflammopharmacology, 2021)

Nonclinical Features in Predictive Modeling of Cardiovascular Diseases: A Machine Learning Approach - Mirza Rizwan Sajid; Noryanti Muhammad; Roslinazairimah Zakaria; Ahmad Shahbaz; Syed Ahmad Chan Bukhari; Seifedine Kadry; A. Suresh (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Effect of co-application of wastewater and freshwater on the physiological properties and trace element content in Raphanus sativus: soil contamination and human health - Natasha; Muhammad Shahid; Aneeza Sardar; Hasnain Anwar; Sana Khalid; Sajid Hussain Shah; Ali Haidar Shah; Muhammad Bilal (Environmental Geochemistry and Health, 2021)

Micro-morphological response of some native dicotyledonous species to particulate pollutants emitted from stone crushing activities - Iftikhar Ahmad; Lubaba Shamsi; Mansoor Hameed; Sana Fatima; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Anum Javaid; Muhammad Asim Sultan (Environmental Science and Pollution Research, 2021)

Optimization, in vitro release and toxicity evaluation of novel pH sensitive itaconic acid-g-poly(acrylamide)/sterculia gum semi-interpenetrating networks - Fauzia Rehman; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Akhtar Rasul; Huma Mahmood; Abid Mehmood Yousaf; Yasser Shahzad; Muhammad Mudassar; Noor Ul Amin Mohsin (DARU Journal of Pharmaceutical Sciences, 2021)

Empirical assessment of rockfall and debris flow risk along the Karakoram Highway, Pakistan - Sajid Ali; Rashid Haider; Wahid Abbas; Muhammad Basharat; Klaus Reicherter (Natural Hazards, 2021)
The Karakoram Highway links north Pakistan with southwest China. It passes through unique geomorphological, geological and tectonic setting. This study focused 200-km-long section of the highway starting from Besham until Chilas. Landslides are frequent and are mostly triggered by torrential rain during Monsoon and Westerlies, leading to highway blockade. Rockfall and debris flow are prime mode of slope failures. Regional to site-specific approach was implemented to assess risk associated with these two modes. Remote sensing-based techniques were used to identify potential hazardous sites, which were further investigated for risk assessment. Modified Pierson’s rockfall hazard rating system (RHRS) rated potential rockfalls, whereas semi-quantitative technique was employed to assess debris flows. Normalized scores of each site shaped the final map, further classified into four zones: very high, high, intermediate and low risk.

Biallelic loss-of-function variants in NEMF cause central nervous system impairment and axonal polyneuropathy - Ashfaque Ahmed; Meng Wang; Gaber Bergant; Reza Maroofian; Rongjuan Zhao; Majid Alfadhel; Marwan Nashabat; Muhammad Talal AlRifai; Wafaa Eyaid; Abdulrahman Alswaid; Christian Beetz; Yan Qin; et al. (Human Genetics, 2021)

Lithofacies and petrography of Miocene Murree Formation, Peshawar basin, NW Pakistan: implications for provenance and paleoclimate - Mustafa Yar; Muhammad Hanif; Muhammad Sajid (Arabian Journal of Geosciences, 2021)

Demographic and morphometric features of pink bollworm, Pectinophora gossypiella (Saunder) (Lepidoptera: Gelechiidae) on four host plants - Muhammad Naeem Mushtaq; Muhammad Arshad; Shahid Majeed; Sajid Aleem Khan (International Journal of Tropical Insect Science, 2021)

Correction to: In Silico Evaluation of Food Derived Bioactive Peptides as Inhibitors of Angiotensin Converting Enzyme (ACE) - Qudsia Yousafi; Jannat Batool; Muhammad Saad Khan; Tamsila Perveen; Muhammad Wasim Sajid; Abrar Hussain; Asim Mehmood; Shahzad Saleem (International Journal of Peptide Research and Therapeutics, 2021)

In Silico Evaluation of Food Derived Bioactive Peptides as Inhibitors of Angiotensin Converting Enzyme (ACE) - Qudsia Yousafi; Jannat Batool; Muhammad Saad Khan; Tamsila Perveen; Muhammad Wasim Sajid; Abrar Hussain; Asim Mehmood; Shahzad Saleem (International Journal of Peptide Research and Therapeutics, 2021)

Survival Strategies in Khavi Grass [Cymbopogon jwarancusa (Jones) Schult.] Colonizing Hot Hypersaline and Arid Environments - Sana Fatima; Mansoor Hameed; Nargis Naz; Syed Mohsan Raza Shah; Mehwish Naseer; Muhammad Sajid Aqeel Ahmad; Muheammad Ashraf; Farooq Ahmad; Sangam Khalil; Iftikhar Ahmad (Water, Air, & Soil Pollution, 2021)

Biochemically Triggered Heat and Drought Stress Tolerance in Rice by Proline Application - Sajid Hanif; Muhammad Farrukh Saleem; Muhammad Sarwar; Muhammad Irshad; Abdul Shakoor; Muhammad Ashfaq Wahid; Haroon Zaman Khan (Journal of Plant Growth Regulation, 2021)

Assessing the perceived impact of exploration and production of hydrocarbons on households perspective of environmental regulation in Ghana - David Ajene Alemzero; Nadeem Iqbal; Sajid Iqbal; Muhammad Mohsin; Ngonadi Josiah Chukwuma; Burhan Ali Shah (Environmental Science and Pollution Research, 2021)

Correction to: Effect of Endoxylanase and Iron Oxide Nanoparticles on Performance and Histopathological Features in Broilers - Hamza Rehman; Muzamal Akram; Mubin Mustafa Kiyani; Muhammad Talha Yasin; Abdul Ghani; Javed Iqbal Saggu; Syed Sajid Hussain Shah; Zafar Mahmood Khalid; Syed Ali Imran Bokhari (Biological Trace Element Research, 2021)

Characterization of fungal flora associated with sternorrhyncha insects of cotton plants - Waheed Anwar; Kiran Nawaz; Muhammad Asim Javed; Adnan Akhter; Ahmad Ali Shahid; Muhammad Saleem Haider; Muhammad Zia Ur Rehman; Sajid Ali (Biologia, 2021)

SARS-CoV-2 nucleocapsid and Nsp3 binding: an in silico study - Muhammad Tahir Khan; Muhammad Tariq Zeb; Hina Ahsan; Abrar Ahmed; Arif Ali; Khalid Akhtar; Shaukat Iqbal Malik; Zhilei Cui; Sajid Ali; Anwar Sheed Khan; Manzoor Ahmad; Dong-Qing Wei; et al. (Archives of Microbiology, 2021)

Plant growth-promoting Bacillus sp. strain SDA-4 confers Cd tolerance by physio-biochemical improvements, better nutrient acquisition and diminished Cd uptake in Spinacia oleracea L. - Muhammad Shahid; Muhammad Tariq Javed; Kashif Tanwir; Muhammad Sohail Akram; Syeda Khola Tazeen; Muhammad Hamzah Saleem; Sajid Masood; Sadia Mujtaba; Hassan Javed Chaudhary (Physiology and Molecular Biology of Plants, 2020)

Methanolic extract of Ephedra ciliata promotes wound healing and arrests inflammatory cascade in vivo through downregulation of TNF-α - Hafiza Sidra Yaseen; Muhammad Asif; Malik Saadullah; Mahrukh; Sajid Asghar; Muhammad Usman Shams; Rizwan Rashid Bazmi; Mohammad Saleem; Hafiz Muhammad Yousaf; Maria Yaseen (Inflammopharmacology, 2020)

Spatially analyzing food consumption inequalities using GIS with disaggregated data from Punjab, Pakistan. - Sana Khushi; Sajid Rashid Ahmad; Ather Ashraf; Muhammad Imran (Food Security, 2020)

The role of sense of place, risk perception, and level of disaster preparedness in disaster vulnerable mountainous areas of Gilgit-Baltistan, Pakistan - Garee Khan; Javed Akhter Qureshi; Anwar Khan; Attaullah Shah; Sajid Ali; Iram Bano; Muhammad Alam (Environmental Science and Pollution Research, 2020)

Frequency of PPAR-γ, FTO and ABCC8 genetic variation in Pakistani cardiovascular smokers - Kanwal Rehman; Ayesha Tahir; Sania Niaz; Sara Shabbir; Komal Jabeen; Amna Faheem; Muhammad Sajid Hamid Akash (Environmental Science and Pollution Research, 2020)

Assessment of health and ecological risks of heavy metal contamination: a case study of agricultural soils in Thall, Dir-Kohistan - Irshad Ullah; Allah Ditta; Muhammad Imtiaz; Sajid Mehmood; Muhammad Rizwan; Muhammad Shahid Rizwan; Amin Ullah Jan; Iftikhar Ahmad (Environmental Monitoring and Assessment, 2020)

Impact assessment of urban development patterns on land surface temperature by using remote sensing techniques: a case study of Lahore, Faisalabad and Multan district - Muhammad Sajid Saleem; Sajid Rashid Ahmad; Shafiq-Ur-Rehman; Muhammad Asif Javed (Environmental Science and Pollution Research, 2020)

Identification of irrigation potential areas, using multi-criteria analysis in Khyber District, Pakistan - Muhammad Waleed; Sajid Rashid Ahmad; Muhammad Asif Javed; Saifullah Samiullah (Environmental Science and Pollution Research, 2020)

First report of post-harvest Fusarium rot caused by Fusarium oxysporum on Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Muhammad Fahim Abbas; Aqleem Abbas; Rana Binyamin (Journal of Plant Pathology, 2020)

Characterization and synthetic biology of lipase from Bacillus amyloliquefaciens strain - Muhammad Tahir Khan; Aman Chandra Kaushik; Qurrat ul ain Rana; Shaukat Iqbal Malik; Anwar Sheed Khan; Dong-Qing Wei; Wasim Sajjad; Shabir Ahmad; Sajid Ali; Ameenullah; Muhammad Irfan (Archives of Microbiology, 2020)

Human exposure to bisphenol A through dietary sources and development of diabetes mellitus: a cross-sectional study in Pakistani population - Muhammad Ejaz Ul Haq; Muhammad Sajid Hamid Akash; Shakila Sabir; Malik Hassan Mahmood; Kanwal Rehman (Environmental Science and Pollution Research, 2020)

Diabetes-associated infections: development of antimicrobial resistance and possible treatment strategies - Muhammad Sajid Hamid Akash; Kanwal Rehman; Fareeha Fiayyaz; Shakila Sabir; Mohsin Khurshid (Archives of Microbiology, 2020)

Integrated Effect of Algal Biochar and Plant Growth Promoting Rhizobacteria on Physiology and Growth of Maize Under Deficit Irrigations - Naseer Ullah; Allah Ditta; Azeem Khalid; Sajid Mehmood; Muhammad Shahid Rizwan; Muhammad Ashraf; Fathia Mubeen; Muhammad Imtiaz; Muhammad Mazhar Iqbal (Journal of Soil Science and Plant Nutrition, 2020)

An unintended challenge of microplastic pollution in the urban surface water system of Lahore, Pakistan - Muhammad Irfan; Abdul Qadir; Mehvish Mumtaz; Sajid Rashid Ahmad (Environmental Science and Pollution Research, 2020)

Oxidative stress risk assessment through heavy metal and arsenic exposure in terrestrial and aquatic bird species of Pakistan - Shamsa Kanwal; Naeem Akhtar Abbasi; Muhammad Jamshed Iqbal Chaudhry; Sajid Rashid Ahmad; Riffat Naseem Malik (Environmental Science and Pollution Research, 2020)

First Investigations on the Removal of Tungsten Species from Water Using Multi-walled Carbon Nanotubes - Ihsanullah Ihsanullah; Muhammad Sajid; Muhamed Kabeer; Ahsan Mushir Shemsi; Muataz Ali Atieh (Water, Air, & Soil Pollution, 2020)

Identification and validation of superior housekeeping gene(s) for qRT-PCR data normalization in Agave sisalana (a CAM-plant) under abiotic stresses - Muhammad Bilal Sarwar; Zarnab Ahmad; Batcho Agossa Anicet; Moon Sajid; Bushra Rashid; Sameera Hassan; Mukhtar Ahmed; Tayyab Husnain (Physiology and Molecular Biology of Plants, 2020)

Organochlorine pesticides in the surrounding soils of POPs destruction facility: source fingerprinting, human health, and ecological risks assessment - Syeda Nazish Ali; Mujtaba Baqar; Mehvish Mumtaz; Uzma Ashraf; Muhammad Naveed Anwar; Abdul Qadir; Sajid Rashid Ahmad; Abdul-Sattar Nizami; Huang Jun (Environmental Science and Pollution Research, 2020)

5-Endo-dig cyclizations in organic syntheses - Muhammad Aamir Sajid; Zulfiqar Ali Khan; Sohail Anjum Shahzad; Syed Ali Raza Naqvi; Muhammad Usman (Molecular Diversity, 2020)

Tillage practices improve rice yield and soil phosphorus fractions in two typical paddy soils - Waqas Ahmed; Muhammad Qaswar; Huang Jing; Dong Wenjun; Sun Geng; Liu Kailou; Meng Ying; Tang Ao; Sun Mei; Li Chao; Xu Yongmei; Sehrish Ali; et al. (Journal of Soils and Sediments, 2020)

First report of post-harvest rot of Citrus reticulata cv. ‘Kinnow’ caused by Rhizopus arrhizus in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Aman Ullah Malik; Mark Lawrence Gleason; Binyamin Rana; Muhammad Amjad Ali (Journal of Plant Pathology, 2020)

First report of Alternaria brown spot of Citrus reticulata cv. ‘Kinnow’ caused by Alternaria arborescens in Pakistan - Anam Moosa; Ayaz Farzand; Muhammad Fahim Abbas; Shahbaz Talib Sahi; Sajid Aleem Khan; Mark Lawrence Gleason (Journal of Plant Pathology, 2020)

First report of Nigrospora sphaerica causing leaf spot of date palm in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Shahbaz Ahmad; Mubeen Sarwar; Aamir Nawaz; Samiya Mahmood Khan; Sajid Ali; Sidra Aslam; Abdul Mannan (Journal of Plant Pathology, 2020)

Adaptations in Imperata cylindrica (L.) Raeusch. and Cenchrus ciliaris L. for altitude tolerance - Khawaja Shafique Ahmad; Ambreen Wazarat; Ansar Mehmood; Muhammad Sajid Aqeel Ahmad; Majid Mahmood Tahir; Fahim Nawaz; Haroon Ahmed; Mohsin Zafar; Aneela Ulfat (Biologia, 2020)

Correlation of MLH1 polymorphisms, survival statistics, in silico assessment and gene downregulation with clinical outcomes among breast cancer cases - Saima Shakil Malik; Ayisha Zia; Sumaira Mubarik; Nosheen Masood; Sajid Rashid; Alice Sherrard; Muhammad Bilal Khan; Muhammad Tahir Khadim (Molecular Biology Reports, 2020)

Response of growth, antioxidant enzymes and root exudates production towards As stress in Pteris vittata and in Astragalus sinicus colonized by arbuscular mycorrhizal fungi - Liu Yizhu; Muhammad Imtiaz; Allah Ditta; Muhammad Shahid Rizwan; Muhammad Ashraf; Sajid Mehmood; Omar Aziz; Fathia Mubeen; Muhammad Ali; Nosheen Noor Elahi; Raina Ijaz; Sha Lele; et al. (Environmental Science and Pollution Research, 2020)

A Novel Approach to Evaluate, Highlight, and Conserve the Geologically Significant Geoheritage Sites from the Peshawar Basin, Khyber Pakhtunkhwa, Pakistan: Insights into Their Geoscientific, Educational, and Social Importance - Muhammad Yaseen; Mukhtiar Ghani; Muhammad Naveed Anjum; Muhammad Sajid; Irfan Ullah Jan; Mubbashir Mehmood; Emad Ullah; Waqas Muzaffir (Geoheritage, 2019)

Anti-pollution cosmetic-based one-step formation of w/o/w multiple emulsion containing D-biotin for skin protection: fabrication and in vitro and in vivo evaluation - Atif Ali; Sajid Iqbal; Aqsa Ilyas; Hira Khan; Muhammad Hassham Hassan Bin Asad; Nighat Fatima; Naveed Akhtar (Drug Delivery and Translational Research, 2019)

Probing the effect of various lipids and polymer blends on clopidogrel encapsulated floating microcarriers - Saba Irshad; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Nadeem Sabir; Adnan Ali; Ahmad Nawaz Khan; Abid Mehmood Yousaf; Talib Hussain; Yasser Shahzad (DARU Journal of Pharmaceutical Sciences, 2019)

Heat treatment effects on chilling injury and disease incidence in sweet orange fruits stored at chilling and non-chilling temperatures - Ijaz Hussain; Abdur Rab; Naqib Ullah Khan; Zarina Bibi; Shah Masaud Khan; Naushad Ali; Muhammad Saeed; Sher Aslam Khan; Sardar Ali; Ghulam Dastagir; Muhammad Sajid (Journal of Consumer Protection and Food Safety, 2019)

Spatial Pattern and Influencing Factor Analysis of Attended Collection and Delivery Points in Changsha City, China - Shuyan Xue; Gang Li; Lan Yang; Ling Liu; Qifan Nie; Muhammad Sajid Mehmood (Chinese Geographical Science, 2019)

Biochemical investigation of association of arsenic exposure with risk factors of diabetes mellitus in Pakistani population and its validation in animal model - Kanwal Rehman; Fiza Fatima; Muhammad Sajid Hamid Akash (Environmental Monitoring and Assessment, 2019)

Different ambient management intervention techniques and their effect on milk production and physiological parameters of lactating NiliRavi buffaloes during hot dry summer of subtropical region - Mehtab Ahmad; Jalees Ahmed Bhatti; Muhammad Abdullah; Rahman Ullah; Qurat ul Ain; Muhammad Sajid Hasni; Mahboob Ali; Abdul Rashid; Imran Qaisar; Ghazunfar Rashid; Rafi Uddin (Tropical Animal Health and Production, 2019)

Effects of biochar and NPK on soil microbial biomass and enzyme activity during 2 years of application in the arid region - Muhammad Azeem; Rifat Hayat; Qaiser Hussain; Muhammad Ibrahim Tahir; Muhammad Imran; Zafar Abbas; Muhammad Sajid; Abdul Latif; Muhammad Irfan (Arabian Journal of Geosciences, 2019)

Effective Role of Biochar, Zeolite and Steel Slag on Leaching Behavior of Cd and Its Fractionations in Soil Column Study - Saqib Bashir; Abdus Salam; Muzammal Rehman; Shahbaz Khan; Allah Bakhsh Gulshan; Javaid Iqbal; Muhammad Shaaban; Sajid Mehmood; Anaam Zahra; Hongqing Hu (Bulletin of Environmental Contamination and Toxicology, 2019)

First report of Alternaria alternata causing postharvest fruit rot of peach in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Aman Ullah Malik; Sidra Aslam; Mubeen Sarwar; Sajid Ali; Muhammad Arslan Khan; Akhtar Hameed; Sohaib Sarfraz (Journal of Plant Pathology, 2019)

Diffusion of China’s coal-fired power generation technologies: historical evolution and development trends - Meizhen Zhang; Tao Lv; Xu Deng; Yuanxu Dai; Muhammad Sajid (Natural Hazards, 2019)

Erosion potential assessment of watersheds through GIS-based hypsometric analysis: a case study of Kurram Tangi Dam - Wasif Yousaf; Syed Ghulam Mohayud-Din-Hashmi; Usman Akram; Urooj Saeed; Sajid Rashid Ahmad; Muhammad Umar; Ambreena Mubashir (Arabian Journal of Geosciences, 2018)

Influence of organic and inorganic passivators on Cd and Pb stabilization and microbial biomass in a contaminated paddy soil - Saqib Bashir; Muhammad Shaaban; Qaiser Hussain; Sajid Mehmood; Jun Zhu; Qingling Fu; Omar Aziz; Hongqing Hu (Journal of Soils and Sediments, 2018)

Concentrations, dietary exposure, and human health risk assessment of heavy metals in market vegetables of Peshawar, Pakistan - Mehboob Alam; Maaz Khan; Anwarzeb Khan; Shah Zeb; Muhammad Amjad Khan; Noor ul Amin; Muhammad Sajid; Abdul Mateen Khattak (Environmental Monitoring and Assessment, 2018)

Pluronic-Based Mixed Polymeric Micelles Enhance the Therapeutic Potential of Curcumin - Muhammad Usman Akbar; Khalid Mahmood Zia; Ahsan Nazir; Jamshed Iqbal; Syeda Abida Ejaz; Muhammad Sajid Hamid Akash (AAPS PharmSciTech, 2018)

Genetic characterization of phenicol-resistant Escherichia coli and role of wild-type repressor/regulator gene (acrR) on phenicol resistance - Muhammad Yaqoob; Li Ping Wang; Jam Kashif; Javed Memon; Sajid Umar; Muhammad Farooq Iqbal; Muhammad Fiaz; Cheng-Ping Lu (Folia Microbiologica, 2018)

Molecular investigation of foot-and-mouth disease virus circulating in Pakistan during 2014-17 - Waqas Ali; Mudasser Habib; Rai Shafqat Ali Khan; Muhammad Ashir Zia; Muhammad Farooq; Sanaullah Sajid; Muhammad Salah Ud Din Shah (Archives of Virology, 2018)

Petrogenesis and tectonic association of rift-related basic Panjal dykes from the northern Indian plate, North-Western Pakistan: evidence of high-Ti basalts analogous to dykes from Tibet - Muhammad Sajid; Jens Andersen; Mohammad Arif (Mineralogy and Petrology, 2018)

Correction to: Increasing water productivity, nitrogen economy, and grain yield of rice by water saving irrigation and fertilizer-N management - Omar Aziz; Saddam Hussain; Muhammad Rizwan; Muhammad Riaz; Saqib Bashir; Lirong Lin; Sajid Mehmood; Muhammad Imran; Rizwan Yaseen; Guoan Lu (Environmental Science and Pollution Research, 2018)

Increasing water productivity, nitrogen economy, and grain yield of rice by water saving irrigation and fertilizer-N management - Omar Aziz; Saddam Hussain; Muhammad Rizwan; Muhammad Riaz; Saqib Bashir; Lirong Lin; Sajid Mehmood; Muhammad Imran; Rizwan Yaseen; Guoan Lu (Environmental Science and Pollution Research, 2018)

Efficiency of C3 and C4 Plant Derived-Biochar for Cd Mobility, Nutrient Cycling and Microbial Biomass in Contaminated Soil - Saqib Bashir; Muhammad Shaaban; Sajid Mehmood; Jun Zhu; Qingling Fu; Hongqing Hu (Bulletin of Environmental Contamination and Toxicology, 2018)

Sugarcane bagasse-derived biochar reduces the cadmium and chromium bioavailability to mash bean and enhances the microbial activity in contaminated soil - Saqib Bashir; Qaiser Hussain; Muhammad Akmal; Muhammad Riaz; Hongqing Hu; Shahzada Sohail Ijaz; Muhammad Iqbal; Shaukat Abro; Sajid Mehmood; Munir Ahmad (Journal of Soils and Sediments, 2018)

Antifungal exploitation of fungicides against Fusarium oxysporum f. sp. capsici causing Fusarium wilt of chilli pepper in Pakistan - Muhammad Rizwan Bashir; Muhammad Atiq; Muhammad Sajid; Muhammad Mohsan; Waseem Abbas; Muhammad Waqar Alam; Muhammad Bashair (Environmental Science and Pollution Research, 2018)

Beating cold by being tough: impact of elevation on leaf characteristics in Phleum himalaicum Mez. endemic to Himalaya - Khawaja Shafique Ahmad; Mansoor Hameed; Abdul Hamid; Fahim Nawaz; Bushra Hafeez Kiani; Muhammad Sajid Aqeel Ahmad; Jiabin Deng; Farooq Ahmad; Imtiaz Hussain; Sana Fatima (Acta Physiologiae Plantarum, 2018)

Comparative Effects of Biochar, Slag and Ferrous–Mn Ore on Lead and Cadmium Immobilization in Soil - Sajid Mehmood; Muhammad Rizwan; Saqib Bashir; Allah Ditta; Omar Aziz; Li Zhe Yong; Zhihua Dai; Muhammad Akmal; Waqas Ahmed; Muhammad Adeel; Muhammad Imtiaz; Shuxin Tu (Bulletin of Environmental Contamination and Toxicology, 2018)

Erratum to: Sub-chronic exposure to low concentration of dibutyl phthalate affects anthropometric parameters and markers of obesity in rats - Khalid Abdul Majeed; Habib ur Rehman; Muhammad Shahbaz Yousaf; Hafsa Zaneb; Imtiaz Rabbani; Sajid Khan Tahir; Muhammad Afzal Rashid (Environmental Science and Pollution Research, 2017)

Sub-chronic exposure to low concentration of dibutyl phthalate affects anthropometric parameters and markers of obesity in rats - Khalid Abdul Majeed; Habib ur Rehman; Muhammad Shahbaz Yousaf; Hafsa Zaneb; Imtiaz Rabbani; Sajid Khan Tahir; Muhammad Afzal Rashid (Environmental Science and Pollution Research, 2017)

PTFE-coated non-stick cookware and toxicity concerns: a perspective - Muhammad Sajid; Muhammad Ilyas (Environmental Science and Pollution Research, 2017)

Nickel stressed responses of rice in Ni subcellular distribution, antioxidant production, and osmolyte accumulation - Muhammad Rizwan; Muhammad Imtiaz; Zhihua Dai; Sajid Mehmood; Muhammad Adeel; Jinchang Liu; Shuxin Tu (Environmental Science and Pollution Research, 2017)

Enzyme inhibitory metabolites from endophytic Penicillium citrinum isolated from Boswellia sacra - Sajid Ali; Abdul Latif Khan; Liaqat Ali; Tania Shamim Rizvi; Sumera Afzal Khan; Javid Hussain; Muhammad Hamayun; Ahmed Al-Harrasi (Archives of Microbiology, 2017)

Prevalence of antibodies to Neospora caninum in the serum of camels (Camelus dromedarius) from central Punjab, Pakistan - Muhammad Mudasser Nazir; Muhammad Oneeb; Muhammad Mazhar Ayaz; Fehmeeda Bibi; Atif Nisar Ahmad; Abdul Waheed; Muhammad Afzal Sajid; Muhammad Tauseef Sultan; Ghulam Yasin; David S. Lindsay (Tropical Animal Health and Production, 2017)

CDK5RAP2 interaction with components of the Hippo signaling pathway may play a role in primary microcephaly - Salil K. Sukumaran; Maria Stumpf; Sarah Salamon; Ilyas Ahmad; Kurchi Bhattacharya; Sarah Fischer; Rolf Müller; Janine Altmüller; Birgit Budde; Holger Thiele; Muhammad Tariq; Naveed Altaf Malik; et al. (Molecular Genetics and Genomics, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Haematology and blood chemistry references values for clinically healthy red-wattled lapwing (Vanellus indicus) - Sajid Umar; Kiran Aqil; Rizwan Qayyum; Muhammad Younus; Qamar-un-Nisa; Shahzad Ali; Muhammad Ali Shah; Muhammad Irfan; Muhammad Usman; Asif Ali; Akbar Ali; Adnan Ayan; et al. (European Journal of Wildlife Research, 2016)

The impact of seasonal variation on organochlorine pesticide residues in buffalo and cow milk of selected dairy farms from Faisalabad region - Muhammad Wasim Sajid; Muhammad Shamoon; Muhammad Atif Randhawa; Muhammad Asim; Abdul Shakoor Chaudhry (Environmental Monitoring and Assessment, 2016)

Comparison of antioxidant enzyme activities and DNA damage in chickpea (Cicer arietinum L.) genotypes exposed to vanadium - Muhammad Imtiaz; Muhammad Adnan Mushtaq; Muhammad Shahid Rizwan; Muhammad Saleem Arif; Balal Yousaf; Muhammad Ashraf; Xiong Shuanglian; Muhammad Rizwan; Sajid Mehmood; Shuxin Tu (Environmental Science and Pollution Research, 2016)

Toxicity of nanoscale metal organic frameworks: a perspective - Muhammad Sajid (Environmental Science and Pollution Research, 2016)

Relationship between in vitro characterization and comparative efficacy of plant growth-promoting rhizobacteria for improving cucumber salt tolerance - Sajid Mahmood Nadeem; Maqshoof Ahmad; Muhammad Naveed; Muhammad Imran; Zahir Ahmad Zahir; David E. Crowley (Archives of Microbiology, 2016)

Synergism of polyamines and plant growth regulators enhanced morphogenesis, stevioside content, and production of commercially important natural antioxidants in Stevia rebaudiana Bert - Shahid Akbar Khalil; Nasir Kamal; Muhammad Sajid; Nisar Ahmad; Roshan Zamir; Naveed Ahmad; Shahid Ali (In Vitro Cellular & Developmental Biology - Plant, 2016)

A novel homozygous splicing mutation of CASC5 causes primary microcephaly in a large Pakistani family - Sandra Szczepanski; Muhammad Sajid Hussain; Ilknur Sur; Janine Altmüller; Holger Thiele; Uzma Abdullah; Syeda Seema Waseem; Abubakar Moawia; Gudrun Nürnberg; Angelika Anna Noegel; Shahid Mahmood Baig; Peter Nürnberg (Human Genetics, 2016)

Amberinone, a new guaianolide from Amberboa ramosa - Muhammad Ibrahim; Iqbal Hussain; Nusrat Hussain; Arruje Hameed; Tahir Farooq; Amjad Hussain; Muhammad Sajid Hamid Akash; Shabbir Hussain (Natural Product Research, 2016)

Co-occurrence of arsenic and fluoride in the groundwater of Punjab, Pakistan: source discrimination and health risk assessment - Atta Rasool; Tangfu Xiao; Zenab Tariq Baig; Sajid Masood; Khan M. G. Mostofa; Muhammad Iqbal (Environmental Science and Pollution Research, 2015)

Reliance of physico-mechanical properties on petrographic characteristics: consequences from the study of Utla granites, north-west Pakistan - Muhammad Sajid; Mohammad Arif (Bulletin of Engineering Geology and the Environment, 2015)

Use of statistical and GIS techniques to assess and predict concentrations of heavy metals in soils of Lahore City, Pakistan - Nayab Alam; Sajid Rashid Ahmad; Abdul Qadir; Muhammad Imran Ashraf; Calvin Lakhan; V. Chris Lakhan (Environmental Monitoring and Assessment, 2015)

Mutation of ATF6 causes autosomal recessive achromatopsia - Muhammad Ansar; Regie Lyn P. Santos-Cortez; Muhammad Arif Nadeem Saqib; Fareeha Zulfiqar; Kwanghyuk Lee; Naeem Mahmood Ashraf; Ehsan Ullah; Xin Wang; Sundus Sajid; Falak Sher Khan; Muhammad Amin-ud-Din; Joshua D. Smith; et al. (Human Genetics, 2015)

Efficacy of silicon priming and fertigation to modulate seedling’s vigor and ion homeostasis of wheat (Triticum aestivum L.) under saline environment - Muhammad Azeem; Naeem Iqbal; Shakila Kausar; M. Tariq Javed; M. Sohail Akram; M. Asim Sajid (Environmental Science and Pollution Research, 2015)

Petrographic and structural controls on geotechnical feasibility of dam sites: implications from investigation at Sher Dara area (Swabi), north-western Pakistan - Yasir Shaheen Khalil; Mohammad Arif; Hasnain Ali Bangash; Muhammad Sajid; Noor Muhammad (Arabian Journal of Geosciences, 2015)

Differential effects of cadmium and chromium on growth, photosynthetic activity, and metal uptake of Linum usitatissimum in association with Glomus intraradices - Amna; Naeem Ali; Sajid Masood; Tehmeena Mukhtar; Muhammad Aqeel Kamran; Mazhar Rafique; M. Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Monitoring and Assessment, 2015)

Exogenous application of silicon at the boot stage decreases accumulation of cadmium in wheat (Triticum aestivum L.) grains - Iqbal Hussain; Muhammad Arslan Ashraf; Rizwan Rasheed; Anum Asghar; Muhammad Asim Sajid; Muhammad Iqbal (Brazilian Journal of Botany, 2015)

Impact of nanoparticles on human and environment: review of toxicity factors, exposures, control strategies, and future prospects - Muhammad Sajid; Muhammad Ilyas; Chanbasha Basheer; Madiha Tariq; Muhammad Daud; Nadeem Baig; Farrukh Shehzad (Environmental Science and Pollution Research, 2015)

Stratigraphic and sedimentological attributes in Hazara Basin Lesser Himalaya, North Pakistan: their role in deciphering minerals potential - Muhammad Umar; Muhammad Amjad Sabir; Muhammad Farooq; Malik Muhammad Saud Sajid Khan; Faridullah Faridullah; Umair Khan Jadoon; Abdul Salam Khan (Arabian Journal of Geosciences, 2015)

Pre-planting exogenous application of gibberellic acid influences sprouting, vegetative growth, flowering, and subsequent bulb characteristics of ‘Ad-Rem’ tulip - Fahad Ramzan; Adnan Younis; Atif Riaz; Sajid Ali; Muhammad Irfan Siddique; Ki-Byung Lim (Horticulture, Environment, and Biotechnology, 2014)

A high virulence and pathotype diversity of Puccinia striiformis f.sp. tritici at its centre of diversity, the Himalayan region of Pakistan - Sajid Ali; Marc Leconte; Hidayatur Rahman; Muhammad Shahab Saqib; Pierre Gladieux; Jérôme Enjalbert; Claude de Vallavieille-Pope (European Journal of Plant Pathology, 2014)

Petrogenesis of granites from the Utla area of Gadoon, north-west Pakistan: Implications from petrography and geochemistry - Muhammad Sajid; Mohammad Arif; M. Tahir Shah (Journal of Earth Science, 2014)

Evaluation of the thiazole Schiff bases as $$\upbeta $$ β -glucuronidase inhibitors and their in silico studies - Khalid Mohammed Khan; Aneela Karim; Sumayya Saied; Nida Ambreen; Xayale Rustamova; Shagufta Naureen; Sajid Mansoor; Muhammad Ali; Shahnaz Perveen; M. Iqbal Choudhary; Guillermo Antonio Morales (Molecular Diversity, 2014)

Inferring the contribution of sexual reproduction, migration and off‐season survival to the temporal maintenance of microbial populations: a case study on the wheat fungal pathogen P uccinia striiformis f.sp. tritici - Sajid Ali; Pierre Gladieux; Hidayatur Rahman; Muhammad S. Saqib; Muhammad Fiaz; Habib Ahmad; Marc Leconte; Angélique Gautier; Annemarie F. Justesen; Mogens S. Hovmøller; Jérôme Enjalbert; Claude de Vallavieille‐Pope (Molecular Ecology, 2014)
Understanding the mode of temporal maintenance of plant pathogens is an important domain of microbial ecology research. Due to the inconspicuous nature of microbes, their temporal maintenance cannot be studied directly through tracking individuals and their progeny. Here, we suggest a series of population genetic analyses on molecular marker variation in temporally spaced samples to infer about the relative contribution of sexual reproduction, off‐season survival and migration to the temporal maintenance of pathogen populations. We used the proposed approach to investigate the temporal maintenance of wheat yellow rust pathogen, P uccinia striiformis f.sp. tritici ( PST ), in the H imalayan region of P akistan. Multilocus microsatellite genotyping of PST isolates revealed high genotypic diversity and recombinant population structure across all locations, confirming the existence of sexual reproduction in this region. The genotypes were assigned to four genetic groups, revealing a clear differentiation between zones with and without B erberis spp., the alternate host of PST , with an additional subdivision within the B erberis zone. The lack of any differentiation between samples across two sampling years, and the very infrequent resampling of multilocus genotypes over years at a given location was consistent with limited over‐year clonal survival, and a limited genetic drift. The off‐season oversummering population in the B erberis zone, likely to be maintained locally, served as a source of migrants contributing to the temporal maintenance in the non‐ B erberis zone. Our study hence demonstrated the contribution of both sexual recombination and off‐season oversummering survival to the temporal maintenance of the pathogen. These new insights into the population biology of PST highlight the general usefulness of the analytical approach proposed.

Hydrogen sulfide ameliorates lead-induced morphological, photosynthetic, oxidative damages and biochemical changes in cotton - Saima Aslam Bharwana; Shafaqat Ali; Muhammad Ahsan Farooq; Basharat Ali; Naeem Iqbal; Farhat Abbas; Muhammad Sajid Aqeel Ahmad (Environmental Science and Pollution Research, 2014)

IL-1Ra and its Delivery Strategies: Inserting the Association in Perspective - Muhammad Sajid Hamid Akash; Kanwal Rehman; Shuqing Chen (Pharmaceutical Research, 2013)

Investigation of equine influenza virus in two geographical regions of Pakistan - Muhammad Sajid; Mansur-ud-Din Ahmad; Muhammad Athar Khan; Muhammad Aftab Anjum; Muhammad Hassan Mushtaq (Tropical Animal Health and Production, 2013)

Erratum to: Three-dimensional quantitative structure–activity relationship (CoMSIA) analysis of bis-coumerine analogues as urease inhibitors - Muhammad Arif Lodhi; Zaheer-ul-Haq; Abdul Wadood; Sajid Iqbal; Khalid Mohammed Khan; Atta-ur-Rahman; Muhammad Iqbal Choudhary (Medicinal Chemistry Research, 2013)

Three-dimensional quantitative structure–activity relationship (CoMSIA) analysis of bis-coumerine analogues as urease inhibitors - Muhammad Arif Lodhi; Zaheer-ul-Haq; Abdul Wadood; Sajid Iqbal; Khalid Mohammad Khan; Atta-ur-Rahman; Muhammad Iqbal Choudhary (Medicinal Chemistry Research, 2013)

Sustained Delivery of IL-1Ra from Pluronic F127-Based Thermosensitive Gel Prolongs its Therapeutic Potentials - Muhammad Sajid Hamid Akash; Kanwal Rehman; Ni Li; Jian-Qing Gao; Hongying Sun; Shuqing Chen (Pharmaceutical Research, 2012)

Elemental contamination in urban parks of Rawalpindi/Islamabad—a source identification and pollution level assessment study - Sajid Iqbal; Mohammad Wasim; Muhammad Tufail; Mohammad Arif; Muhammad M. Chaudhry (Environmental Monitoring and Assessment, 2012)

Extraction, Cleanup, and Chromatographic Determination of Imidacloprid Residues in Wheat - Sajid Iqbal; Riaz Uddin; Sumayya Saied; Mubarik Ahmed; Muhammad Abbas; Sahar Aman (Bulletin of Environmental Contamination and Toxicology, 2012)

Lead (Pb)-Induced Regulation of Growth, Photosynthesis, and Mineral Nutrition in Maize (Zea mays L.) Plants at Early Growth Stages - Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Qaisra Tabassam; Mumtaz Hussain; Humaira Firdous (Biological Trace Element Research, 2011)

Toxic Effect of Nickel (Ni) on Growth and Metabolism in Germinating Seeds of Sunflower (Helianthus annuus L.) - Muhammad Yasin Ashraf; Rumana Sadiq; Mumtaz Hussain; Muhammad Ashraf; M. Sajid Aqeel Ahmad (Biological Trace Element Research, 2011)

Food habits of the snow leopard Panthera uncia (Schreber, 1775) in Baltistan, Northern Pakistan - Muhammad Bilal Anwar; Rodney Jackson; Muhammad Sajid Nadeem; Jan E. Janečka; Shafqat Hussain; Mirza Azhar Beg; Ghulam Muhammad; Mazhar Qayyum (European Journal of Wildlife Research, 2011)

Determination of Multi-residue Insecticides of Organochlorine, Organophosphorus, and Pyrethroids in Wheat - Riazuddin; Muhammad Farhanullah Khan; Sajid Iqbal; Muhammad Abbas (Bulletin of Environmental Contamination and Toxicology, 2011)

Determination of Pesticide Residues in Rice Grain by Solvent Extraction, Column Cleanup, and Gas Chromatography-Electron Capture Detection - Riaz Uddin; Sajid Iqbal; Muhammad Farhanullah Khan; Zahida Parveen; Mubarik Ahmed; Muhammad Abbas (Bulletin of Environmental Contamination and Toxicology, 2011)

Comparative effectiveness of Pseudomonas and Serratia sp. containing ACC-deaminase for improving growth and yield of wheat (Triticum aestivum L.) under salt-stressed conditions - Zahir Ahmad Zahir; Usman Ghani; Muhammad Naveed; Sajid Mahmood Nadeem; Hafiz Naeem Asghar (Archives of Microbiology, 2009)

Monoterpene glycosides from Indigofera hetrantha - Sajid Mehmood; Aziz-Ur-Rahman; Zaheer Ahmad; Nighat Afza; Abdul Malik; Habib Ahmad; Muhammad Iqbal Choudhary (Natural Product Research, 2008)

Series solution for steady flow of a third grade fluid through porous space - Muhammad Sajid; Tasawar Hayat (Transport in Porous Media, 2008)

A simple procedure for simulating surge infiltration using first‐surge infiltrometer data - Sajid Mahmood; Muhammad Latif (Irrigation and Drainage, 2005)
The objective of this study was to modify a ring infiltrometer and to develop a simple and generic technique for simulating cumulative infiltration under constant on‐time surge cycles. A ring infiltrometer was modified by connecting a pipe arm for inward and outward water flow to the ring and from the ring to the pipe to create on–off surge cycles respectively. The Kostiakov infiltration equation was modified by introducing“surge factors” to simulate infiltration data for subsequent surges, using first surge infiltrometer data. The modified form of the Kostiakov equation is called the, “Azeemi–Kostiakov equation”. The unknown parameters of the Kostiakov equation were determined by applying the two‐point technique. Results of the study revealed that the infiltration data simulated by the Azeemi–Kostiakov equation matched closely with those collected from the surge‐ring infiltrometer. A significant reduction in the cumulative infiltration during different surges was also observed which varies from 61 to 84% for the first surge and from 30 to 61% for the subsequent surges. On an overall basis, the significant advantage of the Azeemi–Kostiakov equation is its application in simulating cumulative infiltration of subsequent surges by successfully using limited infiltrometer data. The validity of the Azeemi–Kostiakov equation outside the conditions of the experiments and for varying on–off surge cycles needs to be verified in order to extend its applicability. If this is done, the prior estimation of infiltration for a desired set of on–off surge cycles through this method would permit planning of surge irrigation studies for efficient water management. Copyright © 2005 John Wiley & Sons, Ltd.

Field measurement and simulation of advance rates for continuous and surge irrigated furrows in Pakistan - Muhammad Latif; Sajid Mahmood (Irrigation and Drainage, 2004)
Field tests were conducted with inflow rates of 1.7–2.4 l s −1 to compare the advance rates both in continuous and surge‐irrigated furrows. The furrows were 149 m long, with 0.2–1.5% slopes. Water applied and rate of water advance were measured during five irrigation events. During the first irrigation, a reduction in applied water volume of 23–60% was observed in surge‐irrigated furrows compared with continuous irrigation. It was further noted during the course of the experiments that the surging effect was more pronounced during the first irrigation than in the subsequent irrigation events. However, it was noted that there would be hardly any benefit of the surge for smaller field lengths of 61 m, which are commonly used in Pakistan and many other developing countries. Results simulated by the SIRMOD model revealed that the water front advance curves matched closely with the observed ones in most surge treatments. The simulated performance efficiencies encourage the use and adaptation of surge irrigation in Pakistan, but more field studies are needed for its verification and for making concrete recommendations for its use in farmers' fields. Copyright © 2004 John Wiley & Sons, Ltd.